Method for producing expanded polypropylene resin particles and expanded polypropylene resin particles

JP7630387B2Active Publication Date: 2025-02-17JSP CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021130795
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-10
Publication Date
2025-02-17
Estimated Expiration
2041-08-10

Smart Images

  • Figure 0007630387000010
    Figure 0007630387000010
  • Figure 0007630387000011
    Figure 0007630387000011
  • Figure 0007630387000001
    Figure 0007630387000001
Patent Text Reader

Abstract

To provide: a method for producing a polypropylene resin foamed particle, the method enabling good adhesiveness between foamed particles during in-mold molding to be maintained and furthermore enabling suppression of the occurrence of a problem of blocking and a problem of accumulation of a deposit; and a polypropylene resin foamed particle.SOLUTION: A polypropylene resin particle 10 is provided which has: a core layer 11 containing the polypropylene resin as base material resin; and a coating layer 12 coating the core layer 11, wherein the coating layer 12 of the polypropylene resin particle 10 is composed of the polyethylene-resin, the coating layer 12 of the polypropylene resin particle 10 includes a carbon particle and NOR type hindered amine, a blended ratio of the carbon particles in the coating layer 12 of the polypropylene resin particle 10 is 0.5 wt.% or more and 5 wt.% or less, and a blended ratio of the NOR type hindered amine in the coating layer of the polypropylene resin particle 10 is 0.03 wt.% or more and less than 1 wt.%, and a polypropylene resin foamed particle 20 is also provided which is obtained by foaming and molding the particle 10.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing expanded polypropylene resin beads and expanded polypropylene resin beads. [Background technology]

[0002] Polypropylene resin expanded bead moldings obtained by molding expanded polypropylene resin beads in a mold are used in various applications such as packaging materials, automobile parts, building materials, etc. The expanded beads constituting such expanded bead moldings are produced, for example, as follows.

[0003] First, polypropylene resin particles are dispersed in an aqueous medium containing an inorganic dispersant in a container. Next, the polypropylene resin particles are impregnated with a foaming agent in the container, and the resin particles containing the foaming agent (expandable resin particles) are released from the container together with the aqueous medium to be expanded. In this way, polypropylene resin expanded particles are produced.

[0004] The expanded beads produced as described above may have a coating layer formed on the surface of the expanded bead body in order to enhance the fusion property between the expanded beads during molding in a mold (for example, Patent Documents 1 and 2). Expanded beads having a fusible coating layer are obtained by preparing polypropylene-based resin particles having a core layer and a coating layer provided on the surface of the core layer, and expanding the particles. In this case, from the viewpoint of further enhancing the fusion property, a polyethylene-based resin having a relatively low melting point or softening point compared to the polypropylene-based resin constituting the core layer may be used as the resin constituting the coating layer (for example, Patent Document 3). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6757871 [Patent Document 2] Japanese Patent Application Publication No. 4-118224 [Patent Document 3] Japanese Patent Application Publication No. 10-77359 Summary of the Invention [Problem to be solved by the invention]

[0006] As described above, the expanded beads having a fusible coating layer have improved fusibility between the expanded beads during molding in a mold, but there is still room for improvement in the following points. That is, polypropylene-based resin particles having a coating layer made of a polyethylene-based resin having a relatively low melting point or softening point compared to the core layer may be prone to adhesion (blocking) between the expanded particles depending on the expansion conditions during the expansion process. More specifically, in the expansion process in which expandable resin particles impregnated with a blowing agent are released from a pressure vessel or the like together with an aqueous medium into a relatively low-pressure environment to be expanded, the expanded particles may block each other. Hereinafter, such a problem related to the occurrence of blocking may be simply referred to as a "blocking problem." When in-mold molding is performed using expanded beads that have a blocking problem, there is a risk that the surface properties of the resulting expanded bead molding may be deteriorated.

[0007] Another problem is that when foamed beads having a fusible coating layer are used to produce foamed bead moldings over a long period of time by in-mold molding, there is a risk that deposits originating from the foamed beads will accumulate in parts of the molding die that are easily heated, depending on the shape of the molding die, etc. Such a problem regarding the accumulation of deposits on the molding die will be referred to simply as the "problem of deposit accumulation" below. When the problem of deposit accumulation occurs, there is a risk that the surface properties of the produced foamed bead molding will deteriorate. Such problems of blocking and accumulation of deposits are particularly likely to occur when a polyethylene resin is used as the resin constituting the coating layer.

[0008] The present invention has been made in consideration of the above background, and provides a method for producing expanded polypropylene-based resin beads, and expanded polypropylene-based resin beads, which can suppress the occurrence of blocking problems and the accumulation of deposits while maintaining good fusion properties between the expanded beads during in-mold molding. [Means for solving the problem]

[0009] The method for producing expanded polypropylene-based resin particles of the present invention comprises a dispersion step of dispersing polypropylene-based resin particles in an aqueous medium containing an inorganic dispersant in a container, a foaming agent impregnation step of impregnating the polypropylene-based resin particles with a foaming agent in the container, and an expansion step of releasing the polypropylene-based resin particles containing the foaming agent from the container together with the aqueous medium to expand them, wherein the polypropylene-based resin particles have a core layer containing a polypropylene-based resin as a base resin and a coating layer coating the core layer, the coating layer of the polypropylene-based resin particles is composed of a polyethylene-based resin and contains carbon particles and a NOR-type hindered amine, the blending ratio of the carbon particles in the coating layer of the polypropylene-based resin particles is 0.5% by weight or more and 5% by weight or less, and the blending ratio of the NOR-type hindered amine in the coating layer of the polypropylene-based resin particles is 0.03% by weight or more and less than 1% by weight.

[0010] The expanded polypropylene-based resin beads of the present invention are characterized in that they have an expanded core layer having a polypropylene-based resin as a base resin and a coating layer coating the expanded core layer, the coating layer of the expanded polypropylene-based resin beads being composed of a polyethylene-based resin and containing carbon particles and a NOR-type hindered amine, the blending ratio of the carbon particles in the coating layer of the expanded polypropylene-based resin beads being 0.5% by weight or more and 5% by weight or less, and the blending ratio of the NOR-type hindered amine in the coating layer of the expanded polypropylene-based resin beads being 0.03% by weight or more and less than 1% by weight. Effect of the Invention

[0011] In the method for producing expanded polypropylene resin beads of the present invention, polypropylene resin beads are used which are made of a polyethylene resin and have a coating layer containing a predetermined range of carbon particles and NOR-type hindered amine. This allows the present invention to produce expanded polypropylene resin beads which can suppress the occurrence of blocking problems and deposit accumulation problems while maintaining good fusion between expanded beads during molding in a mold. The expanded polypropylene resin beads produced by the production method of the present invention have the above-mentioned effects, and as a result, expanded bead moldings with excellent surface properties can be stably produced. In addition, the expanded polypropylene resin beads produced by the production method of the present invention allow the production of expanded bead moldings over a long period of time.

[0012] Although the expanded polypropylene resin beads of the present invention have a coating layer made of a polyethylene resin, the coating layer contains a predetermined range of carbon particles and NOR type hindered amine, so that the problem of blocking is unlikely to occur in the expansion step during production. In addition, since the expanded polypropylene resin beads of the present invention have such a coating layer, the occurrence of the problem of accumulation of deposits on the molding die during in-mold molding is suppressed, and the expanded beads can be well fused to each other. Therefore, the expanded polypropylene resin beads of the present invention can provide an expanded bead molding having excellent surface properties by being provided for in-mold molding. In addition, the expanded polypropylene resin beads of the present invention can be used for long-term production of expanded bead moldings. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1A is a cross-sectional view of a polypropylene-based resin particle used in one embodiment of the manufacturing method of the present invention, and FIG. 1B is a cross-sectional view of an expanded polypropylene-based resin particle manufactured by expanding the polypropylene-based resin particle shown in FIG. 1A. [Diagram 2] 1 is an example of a DSC curve obtained according to the method for measuring the heat of transition of plastics described in JIS K7122:1987 in order to obtain the total heat of fusion and the high-temperature peak heat of expanded beads. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The method for producing the expanded polypropylene resin beads of the present invention and the expanded polypropylene resin beads of the present invention will be described below in order. Note that, hereinafter, the method for producing the expanded polypropylene resin beads of the present invention may be simply referred to as the production method of the present invention.

[0015] [Method of manufacturing polypropylene resin foam particles] The manufacturing method of the present invention uses polypropylene-based resin particles having a core layer made of a polypropylene-based resin as a base resin and a coating layer provided on the surface of the core layer to coat the core layer. The coating layer provided on the polypropylene-based resin particles is composed of a polyethylene-based resin and contains carbon particles and NOR-type hindered amine in a predetermined range of blend ratios. Specifically, in the manufacturing method of the present invention, the blend ratio of carbon particles in the coating layer of the polypropylene-based resin particles is 0.5% by weight or more and 5% by weight or less, and the blend ratio of NOR-type hindered amine in the coating layer is 0.03% by weight or more and less than 1% by weight. The production method of the present invention uses the polypropylene-based resin particles having the above-mentioned coating layer, and includes a dispersing step, a foaming agent impregnation step, and a foaming step. The dispersion step is a step of dispersing polypropylene-based resin particles in an aqueous medium containing an inorganic dispersant in a container. The foaming agent impregnation step is a step of impregnating the polypropylene-based resin particles with a foaming agent in a container. The foaming step is a step of releasing the polypropylene-based resin particles containing the foaming agent (expandable resin particles) from the container together with the aqueous medium to cause foaming. In addition to these steps, any appropriate steps can be added to the production method of the present invention without departing from the spirit of the present invention.

[0016] Generally, when expanding resin particles impregnated with a foaming agent are released from a container together with an aqueous medium to be expanded to produce expanded particles, the contents of the container are heated to soften the expandable resin particles in order to expand the expandable resin particles to a desired expansion ratio. In addition, an inorganic dispersant is usually added to the aqueous medium so that the expanded particles do not block each other during expansion. However, in expandable resin particles having a core layer and a coating layer, the coating layer is more likely to soften than the core layer when heated as described above. Therefore, even if an inorganic dispersant is added, blocking problems are likely to occur during expansion. In particular, when attempting to obtain expanded particles with a high expansion ratio, blocking problems tend to occur easily. When foamed beads having such a blocking problem are used for in-mold molding, the foamed beads are less likely to fill the mold, and as a result, the foamed bead molding obtained may have voids, depressions, etc. on the surface, resulting in poor surface properties.

[0017] Generally, the melting point or softening point of a polyethylene resin is lower than the melting point of a polypropylene resin. Therefore, with respect to resin particles having a core layer made of a polypropylene resin, resin particles having a coating layer made of a polyethylene resin are more likely to cause the above-mentioned blocking problem than resin particles having a coating layer made of a polypropylene resin. Therefore, when manufacturing expanded beads using resin particles having a coating layer made of a polyethylene resin, attempts have been made to prevent the blocking problem by adding a large amount of inorganic dispersant to the aqueous medium. However, in this case, there was a problem that the treatment of wastewater, etc. of the aqueous medium containing a large amount of inorganic dispersant became complicated and the burden on the environment increased. In addition, when a large amount of inorganic dispersant was added, there was a problem that the fusibility was impaired depending on the molding conditions, etc.

[0018] In addition to the above-mentioned blocking problem, in general, the coating layer of the expanded beads having a coating layer tends to adhere to the mold during in-mold molding. In other words, when the expanded beads having a coating layer are used, the problem of accumulation of adhesions is likely to occur. In particular, depending on the shape of the mold, heating unevenness may occur depending on the molding part during in-mold molding, and there may be parts of the mold that are easily heated. In such a case, when in-mold molding is performed using the expanded beads having a coating layer, contamination of the mold due to adhesion of the coating layer is more significant. Due to the influence of the adhesions accumulated on the mold, the obtained expanded bead molding may have voids, depressions, etc. formed on the surface, and the surface properties may be deteriorated. Such adhesion problems were particularly likely to occur when resin particles having a coating layer made of a polyethylene resin were used. In particular, when foamed beads having a coating layer made of a polyethylene resin are used to produce foamed bead moldings of complex shapes, the problem of accumulation of adhesion is more pronounced. The reason for this is presumed to be as follows. In other words, when the foamed bead molding has a complex shape, uneven heating during molding in the mold is likely to occur, and some parts are easily heated and some parts are difficult to heat. Therefore, it is necessary to set molding conditions for molding in the mold in accordance with the parts that are difficult to heat. As a result, it is presumed that the molding pressure becomes high overall, and the polyethylene resin that constitutes the coating layer melts and adheres to the inner wall surface of the mold. Although it depends on the shape of the mold, molding conditions, etc., it is possible to suppress the problem of accumulation of deposits as described above by cleaning the mold, for example, every 10 to 30 cycles of in-mold molding. However, since the productivity deteriorates if the mold is cleaned too frequently, it is preferable to clean the mold as infrequently as possible.

[0019] As described above, the coating layer provided to improve the fusion property between the expanded beads during molding in the mold is a factor in the occurrence of the problems of blocking and accumulation of deposits. The improvement of the fusion property between the expanded beads during molding in the mold and the improvement of the blocking problem and the accumulation of deposits are generally contradictory phenomena, and it has been considered difficult to solve both problems at the same time. In particular, when resin particles having a coating layer made of a polyethylene resin are used, the effect of improving the fusion property is high, but the blocking problem and the accumulation of deposits are likely to occur. However, according to the manufacturing method of the present invention having the above-mentioned configuration, it is possible to manufacture expanded polypropylene resin beads that solve these problems at the same time without increasing the amount of inorganic dispersant used during manufacturing. Furthermore, the expanded polypropylene resin beads manufactured by the manufacturing method of the present invention can suppress the occurrence of the problem of accumulation of deposits even when an expanded bead molding is molded by in-mold molding for a long period of time without the need for frequent cleaning of the molding mold as in the past. Due to the excellent effects described above, the expanded polypropylene resin beads produced by the production method of the present invention can provide expanded bead moldings with excellent surface properties, and can be suitably used when producing molded articles with complex shapes.

[0020] The manufacturing method of the present invention will be described in more detail below. FIG. 1 will be used appropriately for the description. FIG. 1 relates to one embodiment of the manufacturing method of the present invention, FIG. (1A) is a cross-sectional view of a polypropylene-based resin particle 10 used in one embodiment of the manufacturing method of the present invention, and FIG. (1B) is a cross-sectional view of a polypropylene-based resin expanded particle 20 manufactured by expanding the polypropylene-based resin particle 10 shown in FIG. (1A). The manufacturing method of the present invention is a method for manufacturing a polypropylene-based resin expanded particle 20 shown in FIG. (1B) (hereinafter, also referred to as an expanded particle 20) by carrying out a predetermined process using a polypropylene-based resin particle 10 (hereinafter, also referred to as a resin particle 10) having a core layer 11 and a coating layer 12 that covers the core layer 11 as shown in FIG. (1A). The expanded particle 20 has a coating layer 22 on its surface. The coating layer 22 is a layer resulting from the coating layer 12 provided on the surface of the core layer 11. 1 is a conceptual diagram shown to facilitate understanding of the manufacturing method of the present invention, and does not limit in any way the particle size of the resin particles 10 and the expanded particles 20, or the thickness ratio of the coating layer 12 of the resin particles 10 and the coating layer 22 of the expanded particles 20. Furthermore, the resin particles 10 and the expanded particles 20 shown in FIG. 1 show cross sections passing through the approximate centers of the particles, but these particles may be spherical or any other shape, such as a cylindrical shape. The coating layer 12 becomes the coating layer 22 provided on the surface of the expanded beads 20 by expanding the resin beads 10 .

[0021] (Polypropylene resin particles) The resin particles 10 used in the manufacturing method of the present invention have a core layer 11 and a coating layer 12 provided on the surface of the core layer 11 to coat the core layer 11. The coating layer 12 is made of a polyethylene resin. The expanded particles 20 obtained by expanding the resin particles 10 having the coating layer 12 have the coating layer 22 on the surface of the foamed core layer 21, which enhances the fusion property between the expanded particles 20 during molding in a mold.

[0022] <Core layer> Base resin: The core layer 11 is composed of a polypropylene-based resin as a base resin. In this specification, the base resin of the core layer 11 refers to a resin that occupies 50% by weight or more of the 100% by weight of the resin that constitutes the core layer 11, and may be one type of polypropylene-based resin or two or more types of polypropylene-based resins. The polypropylene-based resin is exemplified by a propylene homopolymer or a polypropylene-based copolymer containing more than 50% by weight of structural units derived from propylene. Examples of the propylene homopolymer include isotactic polypropylene, syndiotactic polypropylene, and atactic polypropylene. Examples of the polypropylene copolymer include copolymers of propylene and ethylene or α-olefins having 4 or more carbon atoms, such as propylene-ethylene copolymer, propylene-butene copolymer, and propylene-ethylene-butene copolymer, as well as propylene-acrylic acid copolymer, propylene-maleic anhydride copolymer, etc. These copolymers may be block copolymers, random copolymers, or graft copolymers. The above-mentioned polymer may be crosslinked, but is preferably non-crosslinked. From the viewpoint of moldability of the expanded beads in a mold, the polypropylene-based resin is preferably a polypropylene-based copolymer, more preferably one or more selected from a propylene-ethylene copolymer, a propylene-butene copolymer, and a propylene-ethylene-butene copolymer, and further preferably a propylene-ethylene copolymer. In the present invention, a material that contains the polypropylene-based resin as the base resin and that constitutes the core layer 11 may be referred to as a polypropylene-based resin composition. In addition to the polypropylene-based resin as the base resin, the polypropylene-based resin composition may contain other polymers and optional additives within the scope of the present invention.

[0023] Other polymers: Examples of other polymers include thermoplastic resins other than polypropylene resins, such as polyethylene resins, polystyrene resins, polyamide resins, and polyester resins, and elastomers, such as olefin thermoplastic elastomers and styrene thermoplastic elastomers. Two or more of these other polymers may be included. The blending ratio of other polymers in the resin constituting the core layer 11 is preferably 30% by weight or less, more preferably 20% by weight or less, even more preferably 10% by weight or less, even more preferably 5% by weight or less, particularly preferably 3% by weight or less, and most preferably 0% by weight, i.e., it is most preferable that the core layer 11 contains only polypropylene-based resin as a polymer.

[0024] Optional Additives: Examples of optional additives include flame retardants, flame retardant auxiliaries, cell regulators, lubricants, crystal nucleating agents, colorants, conductive materials, and antistatic agents. It is preferable that at least one of carbon particles and NOR type hindered amine is contained in the core layer 11, and it is more preferable that black carbon particles such as carbon black are contained in the core layer 11 as carbon particles, and it is particularly preferable that carbon black and NOR type hindered amine are contained in the core layer 11. By containing an appropriate amount of black carbon particles such as carbon black in the core layer 11, it is possible to provide black expanded beads 20. Also, by containing an appropriate amount of NOR type hindered amine in the core layer 11, it is possible to provide expanded beads 20 with excellent flame retardancy. In addition, black carbon particles refer to carbon particles that are black in color, and broadly include carbon particles that are used as black pigments, such as carbon black, and carbon particles that can impart a black color to resin particles by being mixed with the resin particles. For the carbon particles and NOR type hindered amines usable in the core layer 11, the descriptions of the carbon particles and NOR type hindered amines described in the coating layer 12 described later can be appropriately referred to.

[0025] From the viewpoint of obtaining an expanded bead molding having superior mechanical properties such as rigidity while maintaining the moldability of the expanded beads, the melting point of the polypropylene-based resin constituting the core layer 11 is preferably 130°C or higher and 155°C or lower, more preferably 135°C or higher and 150°C or lower, and even more preferably 140°C or higher and 148°C or lower.

[0026] The melting point of polypropylene resins can be determined based on JIS K7121:1987. In this case, the condition adjustment of the test piece is performed as follows: "(2) Measurement of melting temperature after a certain heat treatment." More specifically, based on the heat flux differential scanning calorimetry method described in JIS K7121:1987, 2 mg of pellet-shaped base resin is used as a test piece, and the temperature is increased from 23°C to 200°C at a heating rate of 10°C / min, then cooled to 23°C at a cooling rate of 10°C / min, and then increased from 23°C to 200°C at a heating rate of 10°C / min again. The melting point of the base resin is determined by the apex temperature of the melting peak determined by the DSC curve obtained when the temperature is increased from 23°C to 200°C at a heating rate of 10°C / min. In addition, when two or more melting peaks appear in the DSC curve, the apex temperature of the melting peak with the largest area is taken as the melting point. Examples of measuring devices include a heat flux differential scanning calorimeter (manufactured by SII Nanotechnology Co., Ltd., model number: DSC7020).

[0027] From the viewpoint of imparting a good black appearance to the expanded bead molding produced by in-mold molding using the expanded beads 20, the blending ratio of black carbon particles such as carbon black in the resin beads 10 is preferably 0.5% by weight or more, more preferably 1.0% by weight or more, even more preferably 1.5% by weight or more, and particularly preferably 2.0% by weight or more. On the other hand, from the viewpoint of preventing the flame retardancy of the expanded bead molding produced by in-mold molding using the expanded beads 20 from being impaired, the blending ratio of carbon particles such as carbon black in the resin beads 10 is preferably 5.0% by weight or less, more preferably 4.0% by weight or less, even more preferably 3.5% by weight or less, and particularly preferably 3.0% by weight or less.

[0028] From the viewpoint that the flame retardancy of the resulting expanded bead molding is unlikely to be impaired even if it contains carbon particles, the blending ratio of the NOR type hindered amine in the resin particles 10 is preferably 0.03 weight % or more, more preferably 0.05 weight % or more, and even more preferably 0.06 weight % or more. On the other hand, from the viewpoint of easily suppressing the variation in the bubble diameter of the resulting expanded bead molding and easily obtaining an expanded bead molding having excellent appearance properties such as color tone, the blending ratio of NOR type hindered amine in the resin particles 10 is preferably 0.4 weight % or less, more preferably 0.3 weight % or less, and even more preferably 0.2 weight % or less.

[0029] When a NOR type hindered amine is blended in the core layer 11, the molecular weight of the NOR type hindered amine contained in the core layer 11 is preferably from 400 to 2500, and more preferably from 500 to 1200. By using a NOR type hindered amine having a molecular weight within the above range in the core layer 11, even when the expanded beads 20 have a low bulk density or contain carbon particles, the resulting expanded bead molding can be stably imparted with flame retardancy. Further, the molecular weight of the NOR type hindered amine contained in the core layer 11 is more preferably 600 or more and 800 or less. If the molecular weight is within the above range, even if the expanded beads 20 containing a colorant such as black carbon particles are used in the core layer 11, the occurrence of unevenness in the color tone of the resulting expanded bead molding can be further suppressed. The reason why these effects are exhibited is not clear, but the following is considered. The NOR type hindered amine having a molecular weight within the above range is easily mixed with the base resin constituting the core layer 11 and is not easily aggregated in the base resin. Therefore, aggregates of the NOR type hindered amine are not easily generated in the composition, and the formation of bubble nuclei derived from the aggregates is suppressed. It is considered that this further reduces the variation in the bubble diameter in the expanded beads 20, and the bubble film thickness of the resulting molding is easily uniform.

[0030] <Coating layer> The coating layer 12 is a layer that coats a part or the whole of the surface of the core layer 11 of the resin particle 10 . For example, the expanded beads 20 obtained by expanding the resin beads 10 having the coating layer 12 can provide an expanded bead molding equivalent to the above-mentioned single-layer expanded bead molding at a steam pressure lower than the minimum steam pressure when the single-layer expanded beads are molded in a mold to produce a single-layer expanded bead molding. The above comparison is performed under conditions in which the single-layer expanded beads and the expanded beads 20 are equivalent in configuration (e.g., expansion ratio, particle size, etc.) other than the presence or absence of the coating layer 12. The single-layer expanded beads refer to expanded beads obtained by expanding a single layer of resin beads composed only of the core layer 11, and the minimum steam pressure refers to the lowest steam pressure during molding in a mold that can sufficiently fuse the single-layer expanded beads to provide a good expanded bead molding. The resin particles 10 are provided with a coating layer 12 made of a polyethylene resin having a melting point or softening point lower than the melting point of the polypropylene resin constituting the core layer 11. The expanded particles 20 obtained by expanding the resin particles 10 having such a coating layer 12 have a coating layer 22 on the surface due to the coating layer 12. Therefore, the expanded particles 20 having the coating layer 22 exhibit good fusion properties during molding in a mold. The softening point (Vicat softening temperature) of the polyethylene resin is measured based on the A50 method of JIS K7206:2016. The melting point of the polyethylene resin constituting the coating layer is measured based on JIS K7121:1987, similar to the melting point of the polypropylene resin constituting the core layer 11. However, in measuring the melting point of the polyethylene resin constituting the coating layer, when two or more melting peaks appear in the DSC curve, the melting point is determined to be the temperature at the apex of the melting peak on the lowest temperature side. In the present invention, a material that contains the polyethylene resin as the base resin, as well as carbon particles and NOR-type hindered amine described below and that constitutes the coating layer 12, may be referred to as a polyethylene resin composition. In addition to the above, the polyethylene resin composition may contain other polymers other than the polyethylene resin as the base resin and any additives.

[0031] As long as the intended object of the present invention can be achieved, the coating layer 12 may be present on the entire surface of the resin particle 10 or on a part of the surface. Typical examples of the resin particle 10 include a cylindrical shape and a roughly spherical shape.

[0032] From the viewpoint of improving the moldability of the expanded beads 20 in a mold, the weight ratio of the coating layer 12 to the total weight of the resin beads 10 is preferably 0.5% by weight or more, more preferably 1% by weight or more, and even more preferably 2% by weight or more. Moreover, from the viewpoint of improving the mechanical strength of the expanded bead molded article obtained by molding in a mold, the weight ratio of the coating layer 12 to the total weight of the resin beads 10 is preferably 15% by weight or less, more preferably 10% by weight or less, and even more preferably 8% by weight or less. By setting the weight ratio of the coating layer 12 in the resin beads 10 within the above range, expanded beads 20 having excellent fusibility can be obtained without impairing the physical properties of the expanded beads produced using the resin beads, and the intended problem of the present invention can be solved. In other words, the physical properties expected for an expanded bead molding obtained by in-mold molding of expanded beads produced using resin beads having a single layer of only the core layer 11 without the coating layer 12 can also be fully exhibited in an expanded bead molding obtained by in-mold molding of expanded beads 20 produced using resin beads 10 having the coating layer 12 in the above ratio.

[0033] Base resin: The coating layer 12 is made of a polyethylene-based resin. Here, being made of a polyethylene-based resin means that the coating layer 12 is made of a polyethylene-based resin as a base resin. In other words, the coating layer 12 contains 50% by weight or more of a polyethylene-based resin in 100% by weight of the resin constituting the coating layer 12. The polyethylene resin is exemplified by an ethylene homopolymer or a polyethylene copolymer containing more than 50% by weight of structural units derived from ethylene.

[0034] Examples of the polyethylene resin include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, and ethylene-methacrylic acid alkyl ester copolymer. The polyethylene resin that is the base resin may be one type of polyethylene resin or a mixed resin of two or more types. These copolymers may be any of block copolymers, random copolymers, and graft copolymers. Among them, from the viewpoint of suppressing peeling between the core layer 11 and the coating layer 12, the polyethylene-based resin is preferably one or more selected from low-density polyethylene, linear low-density polyethylene, and high-density polyethylene, and more preferably linear low-density polyethylene. Low-density polyethylene has a long-chain branched structure and a density of 910 kg / m 3 More than 930kg / m 3 Linear low-density polyethylene refers to a polyethylene resin having a molecular weight of less than 910 kg / m. Linear low-density polyethylene is a copolymer of ethylene and an α-olefin having 4 to 8 carbon atoms, and has a substantially linear molecular chain and a density of 910 kg / m. 3 More than 930kg / m 3 High density polyethylene refers to a polyethylene resin having a density of less than 930 kg / m3. High density polyethylene is an ethylene homopolymer or a copolymer of ethylene and an α-olefin having 4 to 8 carbon atoms, and has a density of 930 kg / m3. 3 This refers to the above polyethylene resins.

[0035] In one preferred embodiment of the present invention, the coating layer 12 contains, as the polyethylene resin, a linear low-density polyethylene polymerized using a metallocene polymerization catalyst. It is more preferred that the polyethylene resin constituting the coating layer 12 is substantially only a linear low-density polyethylene polymerized using a metallocene polymerization catalyst. The coating layer 12 or the coating layer 22 containing the linear low-density polyethylene polymerized using a metallocene polymerization catalyst is particularly likely to be inhibited from peeling off from the core layer 11 or the foamed core layer 21. Therefore, the expanded beads 20 having the coating layer 22 containing the linear low-density polyethylene are more likely to prevent the problem of accumulation of deposits on the molding die during molding in the mold.

[0036] Other polymers: The resin constituting the coating layer 12 may contain other polymers in addition to the polyethylene resin that is the base resin, without departing from the spirit of the present invention. Examples of other polymers include thermoplastic resins other than polyethylene resins, such as polypropylene resins, polystyrene resins, polyamide resins, and polyester resins, and elastomers, such as olefin thermoplastic elastomers and styrene thermoplastic elastomers. Two or more of these other polymers may be included. The blending ratio of other polymers in the resin constituting the coating layer 12 is preferably 30% by weight or less, more preferably 20% by weight or less, even more preferably 10% by weight or less, even more preferably 5% by weight or less, particularly preferably 3% by weight or less, and most preferably 0% by weight, i.e., it is most preferable that the coating layer 12 contains only polyethylene-based resin as a polymer.

[0037] From the viewpoint of further improving the moldability of the expanded beads 20 and easily suppressing the peeling between the coating layer 12 and the core layer 11, the melting point of the polyethylene resin constituting the coating layer 12 is preferably 100°C or more and 125°C or less, more preferably 105°C or more and 120°C or less. From the same viewpoint, the melting point difference [Tmc-Tms] between the melting point Tms of the polyethylene resin constituting the coating layer 12 and the melting point Tmc of the polypropylene resin constituting the core layer 11 is preferably more than 0 and 40°C or less, more preferably 5°C or more and 38°C or less, and even more preferably 10°C or more and 35°C or less. The expanded beads 20 obtained from the resin beads 10 having such a melting point difference are generally more likely to cause the problem of accumulation of deposits, but according to the present invention, this can be suppressed.

[0038] Carbon particles: In the present invention, in order to solve the intended problem, carbon particles are contained in the coating layer 12. Generally, carbon black is used as a colorant for imparting a black color to resin particles or expanded particles. However, according to the present invention, it has been made clear that by blending carbon particles such as carbon black together with a NOR-type hindered amine described below in a predetermined range of amounts in the coating layer 12, it is possible to simultaneously solve the conflicting problems of improving the fusibility of the expanded bead molding, and improving the problems of blocking and accumulation of deposits. The carbon particles contained in the coating layer 12 include a wide range of particles containing carbon, and may be one or more materials selected from carbon black, conductive carbon, carbon nanotubes, graphene, etc. From the viewpoint of being able to better solve the problem of accumulation of deposits, carbon black is preferred as the carbon particles. The particle size of the carbon particles is not particularly limited, but from the viewpoint of being easily mixed into the base resin and not inhibiting the surface smoothness of the expanded beads 20, the particle size is preferably in the range of 1 nm to 500 nm, more preferably 3 nm to 100 nm, even more preferably 5 nm to 50 nm, and even more preferably 10 nm to 30 nm. The particle size of the carbon particles can be determined, for example, by observation with a transmission electron microscope.

[0039] Examples of carbon black that can be used in the coating layer 12 include channel black, roller black, furnace black, thermal black, acetylene black, and ketjen black. Among these, furnace black is preferable as the carbon particles used in the present invention because it has an excellent balance between dispersibility in polyethylene resins and material costs.

[0040] In addition, even if the resin particles have a coating layer containing only NOR type hindered amine without carbon particles among carbon particles and NOR type hindered amine, the blocking problem can be solved. However, when the expanded beads produced using the resin particles are subjected to molding in a mold, the problem of accumulation of deposits may occur. In response to this, by further containing carbon particles such as carbon black in the coating layer, not only the blocking problem but also the problem of accumulation of deposits can be sufficiently solved.

[0041] In the present invention, the content of carbon particles in the coating layer 12 is 0.5% by weight or more and 5% by weight or less. Even if the coating layer contains a NOR-type hindered amine within a specified range, if the blending ratio of the carbon particles contained in the coating layer is outside the above range, there is a risk that desirable expanded beads cannot be provided. That is, if the blending ratio of the carbon particles in the coating layer is too low (including 0% by weight), the surface of the expanded beads may easily adhere to the molding die during molding in the mold, which may easily contaminate the molding die or the surface properties of the resulting expanded bead molding may be deteriorated. On the other hand, if the blending ratio of the carbon particles in the coating layer is too high, there is a risk that the resulting expanded bead molding may be easily flammable. From the viewpoints of easily suppressing adhesion of the coating layer 22 to the molding die during in-mold molding and easily providing an expanded bead molding having a good appearance by suppressing the occurrence of uneven color tone, the blending ratio of the carbon particles in the coating layer 12 is preferably 1.0% by weight or more, more preferably 1.5% by weight or more, and even more preferably 2.0% by weight or more. On the other hand, from the viewpoints of improving the in-mold moldability of the expanded beads 20 and making the resulting expanded bead molding less flammable, the blending ratio of the carbon particles in the coating layer 12 is preferably 4.5% by weight or less, more preferably 4.0% by weight or less, and even more preferably 3.5% by weight or less.

[0042] NOR type hindered amines: The coating layer 12 contains a predetermined range of amounts of NOR type hindered amine. Specifically, the blending ratio of the NOR type hindered amine in the coating layer 12 is 0.03% by weight or more and less than 1% by weight. If the blending ratio of the NOR type hindered amine is out of the above range, there is a risk that desirable expanded beads cannot be provided. That is, if the blending ratio of the NOR type hindered amine in the coating layer is too low (including the case of 0% by weight), there is a risk that the expanded beads are likely to block each other during the expansion process. Similarly, if it is out of the above range, there is a risk that the surface of the expanded beads is likely to adhere to the molding die, which may easily contaminate the molding die, or the surface properties of the resulting expanded bead molding may be reduced. On the other hand, if the blending ratio of the NOR type hindered amine in the coating layer is too high, there is a risk that the fusion property of the expanded bead molding obtained by in-mold molding may be reduced. From the viewpoints of better suppressing the problems of blocking between the expanded beads 20 and accumulation of deposits and making the resulting expanded bead molding less flammable even if it contains carbon particles, the blending ratio of the NOR type hindered amine in the coating layer 12 is preferably 0.05% by weight or more, more preferably 0.08% by weight or more, and even more preferably 0.1% by weight or more. On the other hand, from the viewpoints of well maintaining the fusibility between the expanded beads 20 and enhancing the in-mold moldability of the expanded beads 20, the blending ratio of the NOR type hindered amine in the coating layer 12 is preferably 0.8% by weight or less, more preferably 0.5% by weight or less, and even more preferably 0.3% by weight or less.

[0043] In the present invention, the NOR type hindered amine is a compound having an N-alkoxyl group (>N-OR) structure. Examples of the NOR type hindered amine include compounds having at least one skeleton of the following general formula (1). Any structure is bonded to R in general formula (1). For example, R in general formula (1) is exemplified by an alkyl group, a cycloalkyl group, an aralkyl group, an aryl group, etc. Also, examples of the alkoxyl group in general formula (1) are a cyclohexyloxy group, an octyloxy group, etc. [ka]

[0044] Preferred examples of the NOR type hindered amine used in the present invention include compounds represented by the following chemical formulas (2) to (4). Chemical formula (2) is the product name NOR116 (molecular weight 2261, manufactured by BASF), chemical formula (3) is the product name FP-T80 (molecular weight 681, manufactured by ADEKA Corporation), and chemical formula (4) is the product name Tinuvin 123 (molecular weight 737, manufactured by BASF). [ka] [ka] [ka]

[0045] The coating layer 12 may contain one type of NOR hindered amine or may contain two or more types of NOR hindered amines. Furthermore, the coating layer 12 may contain, in addition to the NOR hindered amine, a hindered amine other than the NOR hindered amine. When the coating layer 12 contains a hindered amine other than the NOR type hindered amine represented by general formula (1), the blending ratio of the other hindered amine may be adjusted within a range that does not deviate from the spirit of the present invention.

[0046] As described above, in the present invention, a NOR type hindered amine is used as the hindered amine contained in the coating layer 12. This allows the present invention to satisfactorily solve the problems of blocking and accumulation of deposits, which are the intended problems of the present invention, while maintaining high fusibility of the molded body. The reason for this is unclear, but it is speculated that this is because the NOR type hindered amine easily attracts an inorganic dispersant to an appropriate degree in an aqueous medium due to electrical interaction, thereby producing expanded beads with an inorganic dispersant adhered to the surface in an appropriate degree.

[0047] From the viewpoints of solving the intended problem of the present invention, as well as of excellent dispersibility in the base resin constituting the coating layer 12 and being less likely to aggregate in the base resin, the molecular weight of the NOR-type hindered amine used is preferably 400 or more and 2500 or less, more preferably 500 or more and 1200 or less, and even more preferably 600 or more and 800 or less.

[0048] When the coating layer 12 contains one type of NOR type hindered amine, the molecular weight of the NOR type hindered amine is the sum of the atomic weights of the atoms constituting the NOR type hindered amine. On the other hand, when the coating layer 12 contains multiple types of NOR hindered amines, the molecular weight of the NOR hindered amine described above is the weighted average of the molecular weights of the NOR hindered amines contained in the coating layer 12. When the molar ratio of each NOR hindered amine contained in the coating layer 12 is unknown, the average molecular weight determined by GPC using polystyrene as a standard substance can be used as the molecular weight of the NOR hindered amine.

[0049] The ratio of the NOR type hindered amine content (wt%) to the carbon particle content (wt%) in the coating layer 12 of the resin particle 10 described above is preferably 0.01 to 0.2, more preferably 0.02 to 0.18, and even more preferably 0.03 to 0.15. By adjusting the content of the carbon particles and the NOR type hindered amine in the coating layer 12 within the above ratio range, when the expanded beads 20 are produced using the coating layer 12, the problems of blocking and accumulation of deposits can be more effectively suppressed while maintaining good fusion properties. As a result, expanded beads 20 with excellent moldability in a mold can be easily obtained.

[0050] The total of the blending ratio (wt%) of the carbon particles and the blending ratio (wt%) of the NOR type hindered amine in the coating layer 12 of the resin particles 10 described above is preferably 0.8 wt% or more and 5.5 wt% or less, more preferably 1.2 wt% or more and 4.5 wt% or less, even more preferably 1.5 wt% or more and 4 wt% or less, and particularly preferably 2 wt% or more and 3.5 wt% or less. By adjusting the total blending ratio of the carbon particles and the blending ratio of the NOR type hindered amine in the coating layer 12 to the above-mentioned range, when the expanded beads 20 are produced using the resin particles 10, the problems of blocking and accumulation of deposits are more easily suppressed while maintaining good fusion properties. As a result, the expanded beads 20 having excellent moldability in the mold can be easily obtained.

[0051] Other Additives: Within the scope of the present invention, the polyethylene resin composition constituting the coating layer 12 may contain one or more other additives. Examples of the other additives include a flame retardant, a flame retardant assistant, a lubricant, a crystal nucleating agent, a conductive material, and an antistatic agent.

[0052] <Method of granulating resin particles> The method for granulating the resin particles 10 is not particularly limited, and any appropriate method can be used as long as the above-described configuration including the core layer 11 and the coating layer 12 is realized.

[0053] Co-extrusion pelletizing method: For example, as a method for granulating the resin particles 10, a method of obtaining resin particles 10 in which a coating layer 12 is laminated on the surface of a core layer 11 by co-extrusion using an extruder can be mentioned. The method of laminating the coating layer 12 on the surface of the core layer 11 by co-extrusion is preferable in that the weight ratio of the coating layer 12 in the resin particles 10 can be easily adjusted, and the coating layer 12 having a relatively uniform thickness can be formed on the resin particles 10 with good productivity. Specifically, the above method is firstly supplied to an extruder for forming a core layer a polypropylene-based resin composition containing a base resin for forming the core layer 11 and a bubble regulator added as necessary, and the base resin, etc. are melted and kneaded in the extruder to obtain a melt-kneaded product for forming the core layer. On the other hand, a polyethylene-based resin composition containing a base resin, carbon particles, NOR-type hindered amine, etc. for forming the coating layer 12 is supplied to an extruder for forming a coating layer, and the base resin, etc. are melted and kneaded in the extruder to obtain a melt-kneaded product for forming the coating layer. Next, the melt-kneaded material for forming the core layer and the melt-kneaded material for forming the coating layer are merged in a co-extrusion die provided downstream of the extruder for forming the core layer, and the melt-kneaded material for forming the coating layer is laminated and extruded around the periphery of the melt-kneaded material for forming the core layer to form a multilayered strand. Next, the strand is cut to a desired size using a pelletizer or the like to obtain a multilayered resin particle 10. The strand is a laminate having a cross section perpendicular to the extrusion direction, such as a circular shape. The resin particle 10 thus obtained has a columnar shape such as a cylindrical shape, a core layer 11 is provided at the center, and does not have a coating layer 12 on both end faces, and a coating layer 12 is provided on the outer peripheral surface other than both end faces. In this way, the core layer 11 may be exposed in a part of the resin particle 10. In the above co-extrusion, when obtaining resin particles 10 having a multilayer structure, it is advisable to adjust the type of base resin of coating layer 12, the ratio of coating layer 12 in resin particles 10, extrusion conditions, cutting conditions, etc. Then, for example, by adopting a method of cutting the strand in a sufficiently softened state, it is possible to obtain resin particles 10 in which substantially the entire surface of core layer 11 is covered with coating layer 12. Furthermore, by subjecting cylindrical resin particles 10 to a spheronization treatment, such as by heating cylindrical resin particles 10 in a dispersion medium at a temperature equal to or higher than the melting point of base resin constituting core layer 11 for a predetermined period of time, it is possible to obtain substantially spherical resin particles 10.

[0054] Granulation by mixing: Another example of a different granulation method for the resin particles 10 is a method in which a core layer 11 formed in advance in a particulate form is mixed with a polyethylene resin composition for forming the coating layer 12 to form the coating layer 12 on the surface of the core layer 11. As an example of such a granulation method, the core layer 11 formed in a particulate form is first placed in a mixer having a mixing function and a heating function to heat the surface of the core layer 11. Next, the polyethylene resin composition for forming the coating layer 12 is placed in the mixer or the like, and the heated core layer 11 and the polyethylene resin composition are mixed to coat the surface of the core layer 11 with the polyethylene resin composition. In this manner, it is possible to obtain resin particles 10 having a multilayer structure and including the coating layer 12. This granulation method is preferable in that the coating layer 12 can be easily formed on the entire surface of the core layer 11.

[0055] (Dispersion process) Next, the dispersion step in the production method of the present invention will be described. The dispersion step is a step of dispersing the resin particles 10 in an aqueous medium placed in a container. The aqueous medium contains an inorganic dispersant. The aqueous medium may also contain any additive other than the inorganic dispersant.

[0056] Aqueous medium: The aqueous medium is a medium for dispersing the resin particles 10 in a container. Examples of the aqueous medium include water, alcohols, glycols, glycerin, and the like, and among them, water is preferred from the viewpoint of ease of wastewater treatment, etc. From the viewpoint of improving the dispersibility of the resin particles 10 and the productivity of the expanded particles 20, the amount of the resin particles 10 added to the aqueous medium is preferably 10 parts by weight or more and 100 parts by weight or less, and more preferably 20 parts by weight or more and 80 parts by weight or less, relative to 100 parts by weight of the aqueous medium.

[0057] Inorganic dispersants: The inorganic dispersant is used to disperse the resin particles 10 well in the aqueous medium and to suppress blocking between the expanded particles 20 during the expansion process. From the viewpoint of easily suppressing blocking between the expanded beads 20 while maintaining the moldability of the expanded beads 20 in the mold, the amount of the inorganic dispersant added is preferably 0.01 parts by weight or more and 2 parts by weight or less, more preferably 0.02 parts by weight or more and 1 part by weight or less, even more preferably 0.03 parts by weight or more and 0.8 parts by weight or less, even more preferably 0.05 parts by weight or more and 0.6 parts by weight or less, and particularly preferably 0.1 parts by weight or more and 0.5 parts by weight or less, relative to 10 or 100 parts by weight of the resin particles. Conventionally, expanded beads having a coating layer made of a polyethylene resin have high fusibility, but tend to cause problems of blocking and accumulation of deposits. However, the expanded beads 20 obtained by the manufacturing method of the present invention have a coating layer 22 containing a predetermined range of carbon black and NOR type hindered amine. Therefore, the expanded beads 20 are less susceptible to the blocking problem, and the occurrence of the problem of accumulation of deposits is suppressed. Furthermore, the occurrence of the problems of blocking and accumulation of deposits can be suppressed without increasing the amount of the inorganic dispersant added. Furthermore, even if the amount of inorganic dispersant used, which was conventionally required when manufacturing the expanded beads 20 having the coating layer 22 made of a polyethylene resin, is reduced, the occurrence of the problems of blocking and accumulation of deposits can be suppressed.

[0058] As the inorganic dispersant, for example, inorganic fine particles such as aluminum oxide, tricalcium phosphate, magnesium pyrophosphate, zinc oxide, kaolin, mica, etc. can be used. These inorganic fine particles may be used alone or in combination of two or more. Among these, it is preferable to use kaolin because it has good compatibility with the NOR type hindered amine contained in the coating layer 12 and has an excellent blocking suppression effect.

[0059] Optional Additives: The aqueous medium may further contain one or more optional additives such as a dispersion aid and a surfactant in addition to the inorganic dispersant. Examples of the dispersion aid include aluminum sulfate. Examples of the surfactant include anionic surfactants such as sodium alkylbenzenesulfonate, sodium dodecylbenzenesulfonate, and sodium alkanesulfonate. The surfactants may be used alone or in combination of two or more. These additives are usually added in an amount of 0.01 to 1 part by weight per 10 or 100 parts by weight of the resin particles.

[0060] (Foaming agent impregnation process) Next, the foaming agent impregnation step will be described. The foaming agent impregnation step is a step of impregnating the resin particles 10 dispersed in an aqueous medium in a container with a foaming agent to obtain expandable resin particles. The foaming agent impregnation step may be performed after the above-mentioned dispersion step, or a part or the whole of the step may be performed overlapping with the dispersion step. The foaming agent impregnation step is appropriately selected from the steps of impregnating the resin particles dispersed in an aqueous medium with a foaming agent in a general expanded bead manufacturing method. For example, a sealed container containing the resin particles 10 is sealed, and a foaming agent is added to the sealed container. In this way, the resin particles 10 are impregnated with the foaming agent to obtain expandable resin particles. The addition of the physical foaming agent to the sealed container may be performed at any timing before the resin particles are foamed. A solid foaming agent may be added to the aqueous medium together with the resin particles 10 during the dispersion process, and then the resin particles 10 may be impregnated with the foaming agent that has become gaseous by heating or the like. In addition, in parallel with the dispersion process or after the dispersion process, the gaseous foaming agent may be pressurized into the sealed container to impregnate the resin particles 10. For example, when carbon dioxide is used as the physical foaming agent, a foaming agent in the form of dry ice may be added to the aqueous medium together with the resin particles 10 during the dispersion process, or gaseous carbon dioxide may be pressurized into the sealed container during or after the dispersion process. When the resin particles 10 are impregnated with the foaming agent, the impregnation of the resin particles 10 with the foaming agent can be promoted by heating and / or pressurizing the inside of the closed container.

[0061] In order to adjust the crystalline state of the expanded beads 20, the above-mentioned dispersion step and / or foaming agent impregnation step may include adjusting the heating rate of the sealed container or holding the sealed container at a predetermined temperature for a predetermined time. For example, it is possible to adjust the DSC curve obtained by heat flux differential scanning calorimetry so that an endothermic peak (high-temperature peak) appears at a higher temperature than the endothermic peak (intrinsic peak) of the base resin constituting the foamed core layer 21 of the expanded beads 20. The expanded beads 20 showing such a high-temperature peak are preferable from the viewpoint of a wider range of molding conditions under which a good expanded bead molded body can be obtained. The above-mentioned adjustment for obtaining the high-temperature peak can be performed, for example, as follows. In the above-mentioned dispersion step and / or foaming agent impregnation step, a one-stage holding step is performed in which the temperature is held at a temperature of (melting point of polypropylene-based resin -20°C) or more and less than (end of melting of polypropylene-based resin) for about 10 to 60 minutes. Thereafter, the temperature is adjusted to a temperature of (melting point of polypropylene-based resin -15°C) to less than (end of melting of polypropylene-based resin). If necessary, a second holding step is performed in which the mixture is held at that temperature for an additional 10 to 60 minutes, and then an expansion step, which will be described later, is performed to produce expanded beads having a high-temperature peak. The total heat of fusion of the resulting expanded beads 20 is preferably 50 J / g to 90 J / g, more preferably 60 J / g to 80 J / g. The endothermic heat of the high-temperature peak (high-temperature peak heat) of the resulting expanded beads 20 is preferably 5 J / g to 40 J / g, more preferably 8 J / g to 30 J / g, and even more preferably 10 J / g to 20 J / g. The total heat of fusion and the high-temperature peak heat of the expanded beads 20 are determined based on JIS K7122:1987 from a DSC curve obtained by using 1 to 3 mg of the expanded beads as a test piece and heating the test piece from 23°C to a temperature 30°C higher than the end of the melting peak at a heating rate of 10°C / min.

[0062] Foaming Agent: The foaming agent used in the present invention is appropriately selected from foaming agents generally used for obtaining expanded beads. For example, a physical foaming agent is preferred as the foaming agent in the present invention. Specific examples of the physical foaming agent include inorganic physical foaming agents and / or organic physical foaming agents. Examples of the inorganic physical foaming agent include carbon dioxide, air, nitrogen, helium, argon, water, etc. Examples of the organic physical foaming agent include aliphatic hydrocarbons such as propane, butane, and hexane, alicyclic hydrocarbons such as cyclopentane and cyclohexane, and halogenated hydrocarbons such as methyl chloride, ethyl chloride, methylene chloride, 2,3,3,3-tetrafluoropropene, trans-1,3,3,3-tetrafluoropropene, and trans-1-chloro-3,3,3-trifluoropropene.

[0063] These physical foaming agents may be used alone or in combination of two or more. Of these foaming agents, preferably, foaming agents mainly composed of inorganic physical foaming agents such as carbon dioxide, nitrogen, and air are used, and more preferably, carbon dioxide is used. In the present invention, "mainly composed of inorganic physical foaming agent" means that the physical foaming agent contains 50 mol% or more of inorganic physical foaming agent. It is preferable that the physical foaming agent contains 70 mol% or more of inorganic physical foaming agent, more preferably 90 mol% or more, and it is even more preferable that the physical foaming agent consists of only inorganic physical foaming agent.

[0064] The amount of the physical foaming agent added is appropriately determined depending on the type of base resin constituting the resin particles 10, the type of foaming agent, the bulk density of the target expanded particles 20, etc. In particular, the amount of the physical foaming agent added may be determined depending on the desired bulk density. For example, when carbon dioxide is used as the physical foaming agent, the amount of carbon dioxide added is preferably 0.1 parts by weight or more and 30 parts by weight or less, more preferably 0.5 parts by weight or more and 15 parts by weight or less, and even more preferably 1 part by weight or more and 10 parts by weight or less, relative to 100 parts by weight of the resin particles 10.

[0065] (Foaming process) After the expandable resin particles are obtained by the above-mentioned foaming agent impregnation step, the foaming step is carried out. The expansion step is a step in which resin particles 10 (expandable resin particles) containing a blowing agent are released from a container together with an aqueous medium and expanded to obtain expanded particles 20. More specifically, the expandable resin particles are expanded by releasing the expandable resin particles together with an aqueous medium under a pressure lower than the internal pressure of the sealed container. This expansion method is preferable because it is easy to obtain expanded particles 20 with a low bulk density.

[0066] However, in the past, when the above-mentioned foaming process was carried out using resin particles with a coating layer, the foamed particles were likely to adhere to each other, and there was a risk of a blocking problem occurring. In particular, when the coating layer was made of a polyethylene-based resin, the blocking problem was significant. In contrast, the manufacturing method of the present invention uses resin particles 10 with a coating layer 12 containing carbon particles and NOR-type hindered amines in a predetermined range, and can sufficiently suppress the occurrence of the above-mentioned blocking.

[0067] Bulk density adjustment: The bulk density of the expanded beads 20 can be adjusted, for example, by appropriately changing the expansion conditions, such as the temperature and pressure in the sealed container when the content of the sealed container is released in the expansion process. Furthermore, when expanded beads 20 having a lower bulk density are desired, a step of expanding the expanded beads in multiple stages may be carried out, such as the two-stage expansion step described below. In the two-stage expansion step, the expanded beads 20 obtained as described above are first stored in a pressurizable sealed container, and a gas such as air is forced into the sealed container to perform a pressurization treatment and increase the internal pressure in the bubbles of the expanded beads 20. Thereafter, the expanded beads 20 are taken out of the sealed container, and heated with steam or hot air to expand the expanded beads 20, thereby carrying out the two-stage expansion step. By carrying out such a two-stage expansion step, it is possible to obtain expanded beads 20 (two-stage expanded beads) having a lower bulk density. In addition, compared with obtaining expanded beads 20 having a low bulk density by a single expansion step, obtaining expanded beads 20 having a low bulk density by performing a two-stage expansion step makes it easier to increase the cell diameter of the finally obtained expanded beads 20. The expanded bead molding produced using the expanded beads 20 obtained by performing the two-stage expansion step can more effectively suppress the occurrence of uneven color tone.

[0068] Bulk density of foam particles: The bulk density of the expanded beads 20 produced by the production method of the present invention is not particularly limited, and can be appropriately determined taking into consideration the use of the expanded bead molding to be molded using the expanded beads. For example, from the viewpoint of achieving light weight of the expanded bead molding, the bulk density of the expanded beads 20 is 500 kg / m 3 It is preferable that the density is less than 100 kg / m 3 More preferably, it is 60 kg / m or less. 3 More preferably, it is 50 kg / m or less. 3 Even more preferably, it is equal to or less than 40 kg / m 3 It is particularly preferred that: The bulk density of the expanded beads 20 is preferably 10 kg / m from the viewpoint of increasing the rigidity of the expanded bead molding. 3 It is preferable that the saturation temperature is 15 kg / m or more. 3 More preferably, it is 18 kg / m or more. 3 More preferably, it is equal to or greater than this.

[0069] Conventional foamed beads having a coating layer have a low bulk density (for example, a bulk density of 60 kg / m 3 The blocking problem was more likely to occur in the foam particles (foam particles below 100%). In contrast, according to the manufacturing method of the present invention, even when the expanded beads have a low bulk density, it is possible to manufacture the expanded beads 20 having the coating layer 12 and suppressing the blocking problem. As a result, it is possible to provide an expanded bead molding having excellent fusibility and surface property, and also having a reduced weight.

[0070] How to measure bulk density: The bulk density of the expanded particles described above is measured by the following method. First, the expanded particles to be measured are left to stand for 24 hours or more in an environment of 23°C temperature, 50% relative humidity, and 1 atm. The expanded particles having the weight W (g) thus obtained are filled into a measuring cylinder, and the filling height of the expanded particles in the measuring cylinder is stabilized by tapping the floor surface with the bottom of the measuring cylinder lightly several times. The bulk volume V (L) of the expanded particles indicated by the graduations on the measuring cylinder is read, and the weight W of the expanded particles is divided by the bulk volume V of the expanded particles (W / V). The value obtained in this way is expressed as kg / m 3 The bulk density of the foamed particles (kg / m 3 ) can be obtained.

[0071] [Polypropylene resin foam particles] Next, the expanded polypropylene resin beads of the present invention will be described. The manufacturing method of the expanded polypropylene resin beads of the present invention is not limited, but the expanded beads can be easily manufactured by the manufacturing method of the present invention described above. The expanded polypropylene resin beads of the present invention are expanded beads 20 having an expanded core layer 21 made of a polypropylene-based resin as a base resin and a coating layer 22 that coats the surface of the expanded core layer 21. The coating layer 22 is composed of a polyethylene-based resin and contains carbon particles and NOR-type hindered amine in a predetermined range. Specifically, the blending ratio of the carbon particles in the coating layer 22 is 0.5% by weight or more and 5% by weight or less, and the blending ratio of the NOR-type hindered amine in the coating layer 22 is 0.03% by weight or more and less than 1% by weight. The expanded beads 20 shown in FIG. (1B) are understood to be the expanded polypropylene resin beads of the present invention. The coating layer 22 present on the surface of the expanded beads 20 may be a foamed layer or a non-foamed layer. The non-foamed layer means a layer that does not substantially have a bubble structure. The coating layer 22 may be partially foamed.

[0072] The foamed core layer 21 is composed of a polypropylene-based resin as a base resin. In this specification, the base resin of the foamed core layer 21 refers to a resin that is 50% by weight or more in 100% by weight of the resin constituting the foamed core layer 21. For the polypropylene-based resin and other materials constituting the foamed core layer 21, the above description of the core layer 11 is referred to as appropriate. Moreover, the coating layer 22 is made of a polyethylene-based resin. Here, being made of a polyethylene-based resin means that the coating layer 22 is made of a polyethylene-based resin as a base resin. In other words, the coating layer 22 contains 50% by weight or more of a polyethylene-based resin in 100% by weight of the resin that constitutes the coating layer 22. For the polyethylene-based resin and other materials that constitute the coating layer 22, the above description of the coating layer 12 may be referred to as appropriate.

[0073] The expanded beads 20 of the present invention described above have the coating layer 22 containing carbon particles and NOR type hindered amine in a predetermined range of blending ratio, and therefore the problems of blocking and accumulation of deposits are effectively suppressed. Therefore, the expanded beads 20 of the present invention have good moldability in a mold, and the expanded bead molding obtained by molding in a mold using the expanded beads 20 has excellent fusibility and surface property. As for the carbon particles and NOR type hindered amine to be blended in the coating layer 22 of the expanded beads 20, the descriptions of the carbon particles and NOR type hindered amine in the above-mentioned production method can be appropriately referred to.

[0074] Ratio of carbon particles in the coating layer 22 of the foamed beads 20: From the viewpoints of easily suppressing adhesion of the coating layer 22 to the molding die during in-mold molding and easily providing an expanded bead molding having a good appearance by suppressing the occurrence of uneven color tone, the blending ratio of the carbon particles in the coating layer 22 is preferably 1.0% by weight or more, more preferably 1.5% by weight or more, and even more preferably 2.0% by weight or more. On the other hand, from the viewpoints of improving the in-mold moldability of the expanded beads 20 and making the resulting expanded bead molding less flammable, the blending ratio of the carbon particles in the coating layer 22 is preferably 4.5% by weight or less, more preferably 4.0% by weight or less, and even more preferably 3.5% by weight or less.

[0075] Ratio of NOR type hindered amine in coating layer 22 of expanded beads 20: From the viewpoints of better suppressing the problems of blocking between the expanded beads 20 and accumulation of deposits and making the resulting expanded bead molding less flammable even if it contains carbon particles, the blending ratio of the NOR type hindered amine in the coating layer 22 is preferably 0.05% by weight or more, more preferably 0.08% by weight or more, and even more preferably 0.1% by weight or more. On the other hand, from the viewpoint of improving the moldability of the expanded beads 20 in the mold, the blending ratio of the NOR type hindered amine in the coating layer 22 is preferably 0.8% by weight or less, more preferably 0.5% by weight or less, and even more preferably 0.3% by weight or less.

[0076] Carbon particle blend ratio in foam beads 20: From the viewpoint of imparting a good black appearance to the expanded bead molding produced by in-mold molding using the expanded beads 20, the blending ratio of black carbon particles such as carbon black in the expanded beads 20 is preferably 0.5% by weight or more, more preferably 1.0% by weight or more, even more preferably 1.5% by weight or more, and particularly preferably 2.0% by weight or more. On the other hand, from the viewpoint of preventing the flame retardancy of the expanded bead molding produced by in-mold molding using the expanded beads 20 from being impaired, the blending ratio of carbon particles in the expanded beads 20 is preferably 5.0% by weight or less, more preferably 4.5% by weight or less, even more preferably 4.0% by weight or less, and particularly preferably 3.5% by weight or less.

[0077] Ratio of NOR type hindered amine in expanded beads 20: From the viewpoint that the flame retardancy of the resulting expanded bead molding is unlikely to be impaired even if it contains carbon particles, the blending ratio of NOR type hindered amine in the expanded beads 20 is preferably 0.03 weight % or more, more preferably 0.05 weight % or more, and even more preferably 0.06 weight % or more. On the other hand, from the viewpoint of improving the appearance characteristics of the resulting expanded bead molding, the blending ratio of the NOR type hindered amine in the expanded beads 20 is preferably 0.4 weight % or less, more preferably 0.3 weight % or less, and even more preferably 0.2 weight % or less.

[0078] Ratio of the blending ratio of the NOR type hindered amine in the coating layer 22 to the blending ratio of the NOR type hindered amine in the expanded beads 20: From the viewpoint of better suppressing blocking problems and deposit accumulation problems, the ratio of the blending proportion of the NOR type hindered amine in the coating layer 22 to the blending proportion of the NOR type hindered amine in the expanded beads 20 is preferably more than 1, more preferably 1.2 or more, and even more preferably 1.5 or more. The upper limit of the ratio of the blending proportion of the NOR type hindered amine in the coating layer 22 to the blending proportion of the NOR type hindered amine in the expanded beads 20 is approximately 50. From the viewpoint of further increasing the fusibility of the expanded beads, the blending proportion of the NOR type hindered amine in the coating layer 22 to the blending proportion of the NOR type hindered amine in the expanded beads 20 is preferably 7.5 or less, more preferably 5 or less.

[0079] Weight percentage of the coating layer 22 in the expanded beads 20: The weight ratio of the coating layer 22 in the expanded beads 20 is preferably 0.5% by weight or more and 10% by weight or less, more preferably 1% by weight or more and 8% by weight or less, and even more preferably 2% by weight or more and 6% by weight or less. When the weight ratio of the coating layer 22 in the total weight of the expanded beads 20 is within the above range, a molded product with excellent fusibility can be obtained without impairing physical properties, and the intended problem of the present invention can be solved. The weight ratio of the coating layer 22 in the expanded beads 20 can be calculated appropriately from the blending ratio of the materials used in producing the resin beads 10.

[0080] Check the mixing ratio: The blending ratio of carbon particles in the coating layer 22 is approximately the same as the blending ratio of carbon particles in the coating layer 12 of the resin particles 10 used in the production of the expanded beads 20. The blending ratio of carbon particles in the expanded beads 20 is approximately the same as the blending ratio of carbon particles in the resin particles 10 used in the production of the expanded beads 20. Therefore, the blending ratio of carbon particles in the coating layer 22 can be appropriately calculated from the blending ratio of carbon particles in the coating layer 12 of the resin particles 10 in the production of the resin particles 10. The blending ratio of carbon particles in the expanded beads 20 can be calculated from the relationship between the weight ratio of the core layer 11 and the coating layer 12, the blending ratio of carbon particles in the core layer 11, and the blending ratio of carbon particles in the coating layer 12 in the production of the resin particles 10. The blending ratio of carbon particles in the coating layer 22 or the expanded beads 20 may be measured directly from a test piece or the expanded beads 20 cut out from the coating layer 22. As a measurement method, a thermogravimetric differential thermal analyzer (i.e., TG-DTA) is used to perform measurements based on JIS K7120:1987 on the test piece or the expanded beads 20, and the blending ratio of the carbon particles contained can be determined based on the mass loss rate from 400°C to 1000°C in the obtained TG curve.

[0081] Similarly, the mixing ratio of the NOR type hindered amine in the coating layer 22 is approximately the same as the mixing ratio of the NOR type hindered amine in the coating layer 12 of the resin particle 10 used in the production of the expanded beads 20. The mixing ratio of the NOR type hindered amine in the expanded beads 20 is approximately the same as the mixing ratio of the NOR type hindered amine in the resin particle 10 used in the production of the expanded beads 20. Therefore, the mixing ratio of the NOR type hindered amine in the coating layer 22 can be appropriately calculated from the mixing ratio of the NOR type hindered amine in the coating layer 12 of the resin particle 10 in the production of the resin particle 10. The mixing ratio of the NOR type hindered amine in the expanded beads 20 can be calculated from the relationship between the weight ratio of the core layer 11 and the coating layer 12, the mixing ratio of the NOR type hindered amine in the core layer 11, and the mixing ratio of the NOR type hindered amine in the coating layer 12 in the production of the resin particle 10. As another method, the blending ratio of the NOR type hindered amine in the coating layer 22 or the expanded beads 20 may be directly measured from a test piece cut out from the coating layer 22 or the expanded beads 20. The measurement method is not particularly limited, but for example, the above-mentioned test piece or the expanded beads 20 is used as a measurement sample and proton nuclear magnetic resonance ( 1 The blending ratio of the NOR type hindered amine contained can be determined by subjecting the composition to 1H-NMR or the like.

[0082] The pretreatment method of the measurement sample and the proton nuclear magnetic resonance ( 1 The following method can be used to quantify the blending ratio of NOR-type hindered amine in a measurement sample by H-NMR, for example. The measurement sample is first pretreated by freeze-pulverizing the measurement sample and weighing out about 2 mg. Then, Soxhlet extraction is performed using chloroform as a solvent to remove the insoluble polymer components. The soluble portion in the Soxhlet extraction is added to acetone to remove the acetone-insoluble oligomer components. The acetone-soluble portion is concentrated, dried, and solidified, and used as a measurement sample for proton nuclear magnetic resonance ( 1 The mixture is subjected to measurement by H-NMR. Proton nuclear magnetic resonance ( 1For example, an AL-400 model manufactured by JEOL Ltd. can be used as the H-NMR spectrometer. Solvent: CDCl3. Measurement nucleus: 1 H, internal standard sample: tetrachloroethane (TCE) is used.

[0083] Average cell diameter of foam particles: The average cell diameter of the expanded beads 20 is preferably 50 μm or more, more preferably 80 μm or more, and even more preferably 100 μm or more from the viewpoint of improving moldability in a mold, and is preferably 220 μm or less, more preferably 200 μm or less, and even more preferably 180 μm or less from the viewpoint of further suppressing unevenness in color tone of the expanded bead molding and improving surface smoothness. The average cell diameter of expanded beads is a value obtained as follows. First, a photograph is taken of a cross section of an expanded bead divided into two equal parts. A straight line is drawn on the photograph so as to roughly halve the area of ​​the expanded bead cross section, and the length L of the line segment from one edge of an expanded bead to the opposite edge is divided by the number N of all the cells in contact with the line segment, giving the value (L / N) as the average cell diameter of one expanded bead. This operation is performed for 10 or more expanded beads, and the arithmetic average value is taken as the average cell diameter of the expanded beads.

[0084] The expanded beads 20 of the present invention can be produced by the above-mentioned production method of the present invention. Therefore, the above-mentioned explanation of the production method of the present invention is appropriately referred to as the explanation of the expanded beads 20 of the present invention.

[0085] How to check the resin that makes up the foam particles: Next, a method for confirming the resin constituting the expanded beads 20 will be described. The expanded beads 20 have an expanded core layer 21 made of a polypropylene-based resin composition containing a polypropylene-based resin as a base resin, and a coating layer 22 made of a polyethylene-based resin composition containing a polyethylene-based resin as a base resin on the surface of the expanded core layer 21. The fact that the expanded beads 20 have such a structure can be determined by an attenuated total reflection (ATR) method using infrared rays. Specifically, it can be determined by checking the infrared absorption spectrum of the surface and cross section of the expanded beads 20 measured by the ATR method.

[0086] The ATR method is a technique in which infrared light is incident on a sample surface with a prism in close contact with it, and the infrared light penetrates slightly into the sample when it is totally reflected by the sample surface, to measure the infrared spectrum from the sample surface to a depth of several micrometers. The ATR method is widely used for surface analysis of various materials because it is easy to measure the spectrum by simply contacting the sample with a prism. However, in the ATR method, the penetration depth into the sample varies depending on the refractive index of the prism material and the angle of incidence of the infrared light, as shown in the following formula (Equation 1). Therefore, when measuring non-uniform materials, it is desirable to keep the measurement conditions constant. For example, it can be seen from the following formula (1) that when the angle of incidence is increased or when a prism with a large refractive index is used, the penetration depth becomes shallower.

number

[0087] A specific method for measuring the infrared absorption spectrum of the surface of the expanded beads 20 by the ATR method will be described below. First, prepare the measurement device used for the ATR method and measure the following conditions at 340 kg / cm 2The surface of the expanded beads is brought into close contact with the prism at a pressing pressure of 1000 MPa, infrared light is incident, and the totally reflected light is measured to obtain an infrared absorption spectrum (without ATR correction). If a coating layer is provided on a portion of the surface of the expanded beads to be measured, the coating layer is brought into close contact with the prism. For example, in the case of cylindrical expanded beads produced by coextrusion, it is advisable to bring the outer peripheral surface of the cylinder, excluding the end faces, into close contact with the prism. <Measurement conditions> Prism: Zinc selenide Incident angle of infrared light: 45° Accumulation count: 512 times Resolution: 4cm -1 Detector: TGS (Triglycine sulfate) Measurement wavenumber range: 600~4000cm -1 Reflection count: 1 Incidentally, an example of a commercially available measuring device is FT / IR-4600 type A (ATR PRO450-S type) manufactured by JASCO Corp. Furthermore, the measurement may be macro measurement or micro measurement.

[0088] The infrared absorption spectrum of the cross section of the expanded bead 20 by the ATR method is measured by the following method. First, the expanded bead 20 is cut into approximately two equal parts passing through its center so that the volumes are approximately equal. Next, the infrared absorption spectrum of the cross section of the expanded bead 20 can be measured by the same method as that for measuring the infrared absorption spectrum of the surface of the expanded bead 20 described above, except that one of the cut surfaces is pressed against a prism.

[0089] When the infrared absorption spectrum of the expanded beads 20 is measured by the ATR method as described above, the following spectrum is detected. That is, wave number 2800~3200cm -1In the infrared absorption spectrum in, two absorbance peaks are detected on the surface of the expanded bead 20, and four absorbance peaks are detected on the cross section of the expanded bead 20. The fact that the above-mentioned number of absorbance peaks are exhibited on each of the surface and cross section of the expanded bead 20 means that the expanded bead 20 has a foamed core layer 21 made of a polypropylene-based resin composition and a coating layer 22 made of a polyethylene-based resin composition. Therefore, for the foamed particles of unknown composition, the infrared absorption spectrum of the surface and cross section was measured by the ATR method, and the wave number was 2800 to 3200 cm -1 It is advisable to check the number of absorbance peaks at 100 nm. This makes it possible to check whether the expanded beads used in the measurement have an expanded core layer made of a polypropylene-based resin as a base resin and a coating layer made of a polyethylene-based resin composition on the surface of the expanded core layer. In order to remove the influence of dust, dirt, organic matter, etc. attached to the surface of the expanded beads, the expanded beads may be washed before carrying out the ATR method described above.

[0090] The above wavenumbers 2800-3200 cm -1 More specifically, the following points are referred to with respect to the peaks exhibited by the expanded particles in the infrared absorption spectrum in Table 1. Note that, details of peaks 1 to 6 relating to the polyethylene resin and the polypropylene resin are shown in Table 1. That is, in the above measurement, the surface of the expanded beads 20 has a viscosity of 2920 cm -1 The peak appearing near 2850 cm (hereinafter referred to as Peak 1) -1 A peak (hereinafter also referred to as Peak 2) appearing near Peak 1 is detected. Peak 1 is a peak due to the antisymmetric stretching vibration of the methylene group (-CH2-) mainly contained in the polyethylene resin. Peak 2 is a peak due to the symmetric stretching vibration of the methylene group (-CH2-) mainly contained in the polyethylene resin. In the above measurement, the cross section of the expanded beads 20 had a thickness of 2950 cm -1 The peak that appears near 2920 cm (hereinafter referred to as peak 3) -1The peak that appears near 2870 cm (hereinafter referred to as peak 4) -1 The peak that appears near 2840 cm (hereinafter also referred to as peak 5) -1 A peak (hereinafter also referred to as peak 6) appearing near the peak 3 is detected. Peak 3 is due to the asymmetric stretching vibration of the methyl group (-CH3) mainly contained in the polypropylene-based resin. Peak 4 is due to the antisymmetric stretching vibration of the methylene group (-CH2-) mainly contained in the polypropylene-based resin. Peak 5 is due to the symmetric stretching vibration of the methyl group (-CH3) mainly contained in the polypropylene-based resin. Peak 6 is due to the symmetric stretching vibration of the methylene group (-CH2-) mainly contained in the polypropylene-based resin.

[0091] Therefore, in the cross section of the expanded beads 20, four peaks (peaks 3 to 6) specific to polypropylene-based resins are confirmed, confirming that the foamed core layer 21 is made of polypropylene-based resin as a base resin. In addition, in the surface of the expanded beads 20, two peaks (peaks 1 and 2) specific to polyethylene-based resins are confirmed, confirming that the coating layer 22 is made of polyethylene-based resin as a base resin. In particular, at a wave number of 2850 cm -1 The peak (peak 2) appearing in the vicinity is a peak specific to polyethylene-based resins, and the appearance of peak 2 confirms that coating layer 22 contains polyethylene-based resin.

[0092] As another method for confirming whether the surface of the expanded beads is composed of a polyethylene resin composition, the following method can be mentioned. Specifically, the infrared absorption spectrum of the surface of the expanded beads is measured by the ATR method described above. Then, at a wave number of 2950 cm -1 Absorbance A at 2950 Wave number for 2920 cm -1 Absorbance A at 2920 Ratio of (A 2920 / A 2950If the absorbance ratio is 2.0 or more, it can be determined that the foamed beads have a surface made of a polyethylene resin composition. -1 The appearance of the peak around 2920 cm is due to the asymmetric stretching vibration of the methyl group (-CH3) mainly contained in polypropylene resins, and is -1 The appearance of a peak around this range is common to polypropylene-based resins and polyethylene-based resins, and when a sample is mainly composed of a polypropylene-based resin as a base resin, the absorbance ratio is less than 2.0, whereas when a sample is mainly composed of a polyethylene-based resin, the absorbance ratio exceeds 2.0. This utilizes the general resin property. The upper limit of the absorbance ratio is approximately 10. In measuring the absorbance ratio, infrared absorption spectra are obtained for the surfaces of at least three expanded beads, and the arithmetic mean value of the obtained absorbance ratios is adopted.

[0093] [Foamed bead molding] An expanded bead molding can be obtained by in-mold molding using the expanded beads 20 of the present invention. For example, the expanded bead molding can be produced as follows. First, the expanded beads 20 are filled into a mold having a cavity corresponding to the shape of the desired expanded bead molding, and the expanded beads 20 filled in the mold are heated by a heating medium such as steam. The expanded beads 20 in the cavity are further expanded by heating and are fused to each other. As a result, the expanded beads 20 are integrated with each other, and an expanded bead molding corresponding to the shape of the cavity is obtained. The expanded bead molded article produced using the expanded beads 20 enjoys the effects of the present invention, has excellent fusibility and surface properties, and the molded article density can be adjusted within an appropriate range, and can therefore be suitably used for various applications such as packaging materials, automobile parts, and building materials.

[0094] Molded body density: The density of the expanded bead molding obtained by using the expanded beads 20 is not particularly limited. From the viewpoint of excellent balance between light weight and mechanical properties such as rigidity, the density is preferably 10 kg / m 3 More than 500kg / m 3 It is preferable that the thickness is less than 15 kg / m 3 More than 100kg / m 3 The density of the expanded bead molding is calculated by dividing the weight of the expanded bead molding by the volume calculated based on the outer diameter. If it is difficult to calculate the volume from the outer diameter, the volume of the expanded bead molding can be determined by a submersion method. EXAMPLES

[0095] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. For each of the examples and comparative examples carried out as described below, the bulk density, total heat of fusion, high-temperature peak heat, average cell diameter, and absorbance by the ATR method of the expanded beads were measured, and the productivity during in-mold molding and the molded article of the polypropylene resin expanded beads produced using the expanded beads were evaluated. The measurement results and evaluation results are shown in Tables 3 and 4. In Tables 3 and 4, the carbon black used as the carbon particles is written as CB. The expanded beads used for measuring the physical properties of the expanded beads were left in an environment of 23°C temperature, 50% relative humidity, and 1 atm for 24 hours or more to adjust their condition. The blending ratio of the NOR type hindered amine in the expanded beads and the coating layer provided on the expanded beads, and the blending ratio of the carbon black were calculated from the addition ratio of the materials used in producing the resin beads.

[0096] <Example 1> (Preparation of Resin Particles) A manufacturing device was prepared, which was equipped with an extruder for forming a core layer with an inner diameter of 50 mm, a die for forming a multilayer strand attached to the downstream side of the extruder for forming a core layer, and an extruder for forming a coating layer with an inner diameter of 30 mm. Note that the downstream side of the extruder for forming a coating layer was connected to the die for forming a multilayer strand, and the manufacturing device was configured to be capable of laminating the molten mixture for forming each layer in the die and to be capable of co-extrusion. The resin constituting the core layer was a polypropylene-based resin (PP1) shown in Table 2. As the core layer forming material (polypropylene-based resin composition) constituting the core layer, in addition to the above-mentioned resin, 0.1% by weight of zinc borate was used as a bubble adjusting agent in 100% by weight of the core layer molding material, and carbon black (furnace black, particle size 18 nm) and NOR type hindered amine (manufactured by BASF, product name NOR116 (molecular weight 2261)) were used in the blending ratios shown in Table 3, and these were fed to a core layer forming extruder and melt-kneaded. The resin constituting the coating layer was a polyethylene resin (PE1) shown in Table 2. As the coating layer forming material (polyethylene resin composition) constituting the coating layer, in addition to the above resin, carbon black (furnace black, particle size 18 nm) and NOR type hindered amine (manufactured by BASF, product name NOR116 (molecular weight 2261)) were used in the blending ratios shown in Table 3, and these were fed to a coating layer forming extruder and melt-kneaded. The molten mixtures for forming each layer obtained by melt kneading as described above were introduced into a die for forming a multilayer strand and merged inside the die, and a multilayer strand having a two-layer structure (coating layer / core layer structure) was extruded from the holes in the die attached to the downstream side of the die. The extruded strand was cooled with water and cut with a pelletizer to obtain cylindrical resin particles with an average weight of 1.0 mg per piece.

[0097] (Preparation of Expanded Beads) 1 kg of the obtained resin particles was supplied together with 3 L of water as an aqueous medium into a sealed container having a capacity of 5 L. In addition, 0.6 parts by weight of kaolin as an inorganic dispersant, 0.008 parts by weight (as an active ingredient) of a surfactant (product name: NEOGEN, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., sodium dodecylbenzenesulfonate), and 0.02 parts by weight of aluminum sulfate were added to the sealed container relative to 100 parts by weight of the resin particles. Next, carbon dioxide was injected as a blowing agent into the sealed container, and the pressure was increased to 2.0 MPa (G) in gauge pressure. The pressures marked with (G) are gauge pressures, that is, pressure values ​​based on atmospheric pressure. After that, the sealed container was heated to the foaming temperature (149.5°C) at a rate of 2°C / min while stirring, and the temperature was maintained for 15 minutes. This allowed the endothermic curve of the resulting expanded beads to have a high-temperature peak in the DSC measurement. The contents of the sealed container (resin particles and water) are then released under atmospheric pressure to a bulk density of 60 kg / m 3 The same process as described above was repeated several times to obtain a sufficient amount of expanded beads for the evaluation described below.

[0098] The first-stage expanded particles obtained as described above were left to stand for 24 hours in an environment of 23°C temperature, 50% relative humidity, and 1 atm for curing. The cured first-stage expanded particles were then filled into a pressurizable airtight container, and the pressure in the airtight container was increased from normal pressure to pressurize the expanded particles. The pressurized state of the expanded particles was maintained for a predetermined time, allowing air to be impregnated into the bubbles of the expanded particles. The first-stage expanded particles were then removed from the airtight container, and first-stage expanded particles with an internal bubble pressure of 0.5 MPa (G) were obtained. The first-stage expanded particles were then fed into a second-stage expansion device. Steam was fed into the device to expand the first-stage expanded particles, resulting in a bulk density of 27 kg / m 3 The expanded beads obtained by the two-stage expansion were used for the following measurements and for producing expanded bead moldings.

[0099] (bulk density of expanded particles) The expanded particles to be measured were left to cure for 24 hours or more in an environment of 23°C temperature, 50% relative humidity, and 1 atm. The cured expanded particles (weight W; 30 g) were filled into a measuring cylinder, and the bottom of the measuring cylinder was lightly tapped on the floor several times to stabilize the filling height of the expanded particles in the measuring cylinder. The bulk volume V (L) of the expanded particles indicated by the graduations on the measuring cylinder was read. The weight W of the expanded particles was then divided by the bulk volume V (W / V). The value obtained in this way was expressed in kg / m 3 The bulk density of the foamed particles (kg / m 3 ) was calculated.

[0100] (Total heat of fusion and high-temperature peak heat of expanded beads) The test specimen was approximately 1 mg of foamed particles. The test specimen was heated and melted according to the method for measuring the heat of transition of plastics described in JIS K7122:1987, and a DSC curve was obtained. The measurement temperature range was from 23°C to a temperature 30°C higher than the end of the melting peak of the test specimen, and the heating rate was 10°C / min. The DSC curve thus obtained is shown in Figure 2. A straight line was drawn on the DSC curve connecting point I, which corresponds to 80°C on the DSC curve, and point II, which corresponds to the melting end temperature of the expanded beads. The melting end temperature is the high-temperature end point of high-temperature peak b, and is the intersection point of high-temperature peak b and the baseline on the higher temperature side of high-temperature peak b on the DSC curve. As shown in Figure 2, a straight line was drawn connecting points I and II, and then the intersection point of the line passing through the maximum point III between the intrinsic peak a and the high-temperature peak b and parallel to the vertical axis of the graph with the line connecting points I and II was designated as IV. The areas of the straight line connecting points I and IV, the straight line connecting points III and IV, and the DSC curve connecting points I and III were defined as the area of ​​intrinsic peak a. The area of ​​the portion (shaded portion) surrounded by the straight line connecting points IV and II, the straight line connecting points III and IV, and the DSC curve connecting points III and II was defined as the area of ​​high-temperature peak b. The sum of the areas of intrinsic peak a and high-temperature peak b determined as above was defined as the value of the total heat of fusion of the expanded beads, and the area of ​​high-temperature peak b was defined as the value of the high-temperature peak heat of the expanded beads.

[0101] (Average bubble diameter of expanded particles) A photograph of the cross section of an expanded bead divided into two was taken. A straight line was drawn on the photograph so as to roughly halve the area of ​​the expanded bead cross section, and the length L of the line segment from one edge of the expanded bead to the opposite edge was divided by the number N of all the bubbles in contact with the line segment (L / N) to determine the average bubble diameter of one expanded bead. This operation was performed for 10 or more expanded beads, and the arithmetic average value was determined to be the average bubble diameter of the expanded beads.

[0102] (ATR analysis of foam particles) Measurement was performed by macro ATR. The foamed particles obtained above were analyzed using a commercially available ATR analyzer (manufactured by JASCO Corporation; FT / IR-4600 type A (ATR PRO450-S type)). The analysis conditions were as follows. <Measurement conditions> Prism: Zinc selenide Incident angle of infrared light: 45° Accumulation count: 512 times Resolution: 4cm -1 Detector: TGS (Triglycine sulfate) Measurement wavenumber range: 600~4000cm -1 Reflection count: 1

[0103] The surface of the expanded beads was analyzed by bringing the outer peripheral surface of the expanded beads, excluding both end faces, into contact with a prism, while the cross section of the expanded beads was analyzed by bringing the cut surface into contact with a prism using a sample cut at approximately half the positions of both end faces of the expanded beads in a direction perpendicular to the axial direction of the column. In the ATR analysis, the wavenumbers of the foamed particle surface and cross section were 2800 to 3200 cm -1 The number of absorbance peaks and the absorbance of the peaks at wavenumber 2950 cm were also measured. -1 Absorbance A at 2950 Wave number for 2920 cm -1 Absorbance A at 2920 Ratio of (A 2920 / A 2950 ) was obtained. In all of the Examples and Comparative Examples 1 to 5, two peaks were detected on the expanded bead surface (peaks 1 and 2 shown in Table 1), and four peaks were detected on the expanded bead cross section (peaks 3 to 6 shown in Table 1). That is, it was confirmed that in all of the expanded beads, polypropylene-based resin was present in the cross section, and polyethylene-based resin was present on the surface. In Comparative Example 6, four peaks were detected on both the expanded bead surface and the expanded bead cross section (peaks 3 to 6 shown in Table 1). That is, it was confirmed that polypropylene-based resin was present in both the cross section and the surface of the expanded bead of Comparative Example 6, which is a single layer. In addition, in all of the Examples and Comparative Examples 1 to 5, the ratio of absorbance on the surface of the expanded beads (A 2920 / A 2950 ) was 2.0 or more. That is, it was confirmed that the polyethylene resin was present on the surface of each of the expanded beads. In addition, in Comparative Example 6, the ratio of absorbance (A 2920 / A 2950 ) was less than 2.0. That is, it was confirmed that the polypropylene-based resin was present both on the cross section and on the surface of the expanded beads of Comparative Example 6, which was a single layer. In measuring the absorbance ratio, infrared absorption spectra were obtained for the surfaces of three expanded beads, and the arithmetic average value of the obtained absorbance ratios was used.

[0104] (Production of foamed bead moldings) The obtained expanded beads were filled in a pressurizable sealed container, and the pressure in the sealed container was increased from normal pressure to pressurize the expanded beads. The expanded beads were kept in a pressurized state for a predetermined time to impregnate the bubbles of the expanded beads with air. Thereafter, the expanded beads were taken out of the sealed container to obtain expanded beads with an internal pressure of 0.1 MPa (G) in the bubbles of the expanded beads. The expanded beads were filled in a mold (metal mold) having a molding cavity capable of molding a box-shaped molded body having a length of 200 mm, a width of 150 mm, a height of 50 mm, and a bottom wall and side wall thickness of 10 mm, and heated by the following heating method. The heating method was performed by supplying steam to the mold with the drain valves provided on both sides of the mold open to perform preheating (exhaust process). Thereafter, steam was supplied from one side of the mold to heat it, and further steam was supplied from the other side of the mold to heat it. Subsequently, steam was supplied from both sides of the mold at a molding heating steam pressure of 0.26 MPa (G) to heat it. After heating, the pressure was released and the expanded bead molding was cooled with water until the surface pressure due to the expansion force of the expanded bead molding reached 0.04 MPa (G), after which the mold was opened and the expanded bead molding was taken out. The expanded bead molding obtained was cured in an oven at 80°C for 12 hours and then slowly cooled to room temperature to obtain a box-shaped expanded bead molding with an open top. The expanded bead molding was a box-shaped expanded bead molding with an open top and outer dimensions of 200 mm length x 150 mm width x 50 mm height, with the bottom and side walls each having a thickness of 10 mm, and when the surface of 200 mm length x 150 mm width is taken as the bottom surface, the top surface side is open.

[0105] <Example 2> Resin particles were prepared in the same manner as in Example 1, except that the blending ratio of the NOR type hindered amine added to the coating layer forming material was changed to the value shown in Table 3. Using these resin particles, expanded beads and expanded bead moldings were obtained in the same manner as in Example 1.

[0106] <Examples 3 and 4> Resin particles were prepared in the same manner as in Example 1, except that the blending ratios of the NOR type hindered amine and carbon black added to the coating layer forming material were changed to the values ​​shown in Table 3. Using these resin particles, expanded beads and expanded bead moldings were obtained in the same manner as in Example 1.

[0107] <Example 5> Resin particles were prepared in the same manner as in Example 2, except that the blending ratios of the dispersant and the dispersion aid (surfactant) in the expansion step were changed to the values ​​shown in Table 3. Using these resin particles, expanded beads and expanded bead moldings were obtained in the same manner as in Example 1.

[0108] <Examples 6 and 7> Except for changing the type of NOR-type hindered amine added to the core layer-forming material and the coating layer-forming material, resin particles were prepared in the same manner as in Example 1. Using these resin particles, expanded beads and expanded bead moldings were obtained in the same manner as in Example 1. As the NOR type hindered amine, "ADEKA CORPORATION, product name FP-T80 (molecular weight 681)" was used in Example 6, and "BASF SE, product name Tinuvin 123 (molecular weight 737)" was used in Example 7.

[0109] <Example 8> Resin particles were prepared in the same manner as in Example 1, except that the type of polyethylene resin used in the coating layer-forming material was changed to a polyethylene-based resin (PE2) shown in Table 2. Using these resin particles, expanded beads and expanded bead moldings were obtained in the same manner as in Example 1.

[0110] In all of the Examples, good fusion was achieved, and no blocking or accumulation of deposits occurred, resulting in the production of expanded bead moldings with excellent surface properties. In Examples 6 and 7, which used a NOR-type hindered amine with a smaller molecular weight, the unevenness of color tone was well suppressed, resulting in the production of expanded bead moldings with particularly excellent appearance.

[0111] <Comparative Examples 1 and 2> Resin particles were prepared in the same manner as in Example 1, except that the blending ratios of the NOR type hindered amine and carbon black added to the coating layer forming material were changed to the values ​​shown in Table 4. Using these resin particles, expanded beads and expanded bead moldings were obtained in the same manner as in Example 1. Since the coating layer of the resin particles prepared in Comparative Example 1 did not contain NOR-type hindered amine, blocking between the expanded beads occurred when the expanded beads were used in the expansion process. Furthermore, when the expanded beads prepared in Comparative Example 1 were repeatedly molded in the same mold, a part of the coating layer adhered to and accumulated on the inner surface of the mold. As a result, the surface properties of the obtained expanded bead molding were impaired. Since the coating layer of the resin beads prepared in Comparative Example 2 did not contain carbon black, when the expanded beads prepared using the coating layer were repeatedly molded in the same mold, a part of the coating layer adhered to and accumulated on the inner surface of the mold, resulting in a deterioration in the surface properties of the obtained expanded bead molding.

[0112] <Comparative Example 3> Resin particles were prepared in the same manner as in Comparative Example 1, except that the type of polyethylene resin used in the coating layer-forming material was changed to a polyethylene-based resin (PE2) shown in Table 2, and the blending ratio of the NOR-type hindered amine added to the coating layer-forming material was changed to the value shown in Table 4. Using these resin particles, expanded beads and expanded bead moldings were obtained in the same manner as in Comparative Example 1. The coating layer in the resin particles prepared in Comparative Example 3 exceeded the range of the blending ratio of the NOR type hindered amine specified in the present invention. Therefore, the expanded beads prepared using this were used to perform in-mold molding, and the expanded beads molding obtained had impaired fusibility.

[0113] <Comparative Examples 4 and 5> Resin particles were prepared in the same manner as in Example 1, except that a hindered amine other than the NOR-type hindered amine was added to the coating layer-forming material. Using these resin particles, expanded beads and expanded bead moldings were obtained in the same manner as in Example 1. In Comparative Example 4, "BASF, product name Tinuvin 622" was used as the NR-type hindered amine, and in Comparative Example 5, "BASF, product name Tinuvin 770" was used as the NH-type hindered amine. The coating layer in the resin particles prepared in Comparative Examples 4 and 5 does not contain a NOR type hindered amine, but contains a hindered amine other than the NOR type hindered amine. Therefore, when the expanded beads prepared using the coating layer were repeatedly molded in the same mold, a part of the coating layer adhered to the inner surface of the mold and accumulated. As a result, the surface properties of the obtained expanded bead molding were impaired.

[0114] <Comparative Example 6> Single-layer resin beads having no coating layer were prepared. Using these resin beads, expanded beads and expanded bead moldings were obtained in the same manner as in Example 1. Since the resin particles prepared in Comparative Example 6 did not have a coating layer, the expanded beads prepared using these particles were used to perform in-mold molding to obtain an expanded bead molding having poor fusion properties.

[0115] <Productivity evaluation> Presence or absence of blocking during foaming process: The expanded particles were sieved through a punching screen with a diameter of 6 mm, pitch of 8 mm, and opening rate of 35%, and the weight of the expanded particles remaining on the screen was measured. The weight of the expanded particles remaining on the screen relative to the weight of all the expanded particles sieved was measured. The ratio of the weight of the expanded particles remaining on the screen relative to the weight of all the expanded particles sieved was calculated, and the occurrence of blocking was evaluated according to the following criteria. None: The weight percentage of the foam particles remaining on the screen was less than 5% by weight. Present: The weight percentage of the foamed particles remaining on the screen was 5% by weight or more.

[0116] Whether or not resin adheres to the mold when molding is repeated: Thirty cycles of molding were carried out continuously using the same mold and molding conditions. After molding, the mold was visually inspected for the presence or absence of resin adhesion, and the presence or absence of resin adhesion was evaluated according to the following criteria. None: No adhesion was observed. Yes: Partial adhesion was observed.

[0117] <Evaluation of Molded Products> Thirty cycles of in-mold molding were carried out continuously using the same mold and molding conditions. The foamed bead molding obtained in the 30th cycle was used to evaluate the molding as follows. The molding pressure (MPa(G)) during in-mold molding is also shown in Tables 3 and 4.

[0118] Density of foamed bead compacts: The weight of the expanded bead molding is divided by the volume calculated based on the dimensions to give the molding density (kg / m 3 ) was decided.

[0119] Weldability: The fusion property of the expanded bead molding was determined based on the ratio of the number of foamed beads that were broken among the foamed beads exposed on the fracture surface when the expanded bead molding was broken. Specifically, a test piece (100 mm long x 100 mm wide x thickness: thickness of molding) was cut from the center of the expanded bead molding, and a cutter knife was used to make a cut of about 5 mm in the thickness direction of each test piece, and the test piece was broken from the cut part. Next, the number of foamed beads (n) present on the fracture surface of the expanded bead molding and the number of foamed beads that were broken (b) were measured, and the ratio (b / n) of (b) and (n) was expressed as a percentage to obtain the fusion rate (%), and was evaluated as follows. ○: Fusion rate is 80% or more. △: Fusion rate is less than 80% and more than 40%. ×: Fusion rate is less than 40%.

[0120] Superficiality: Thirty cycles of molding in the mold were carried out continuously. After the 30th cycle, the surface of the foamed bead molding obtained was visually inspected for the presence of unintended depressions (depressions thought to have been caused by deposits on the mold) and gaps (voids) between the foamed beads, and evaluated according to the following criteria. ◯: Almost no gaps and / or depressions were observed on the surface of the expanded bead molding. ×: Gaps and / or depressions were found scattered on the surface of the expanded bead molding. In the evaluation of x, the dents and gaps were mainly formed in the bottom wall of the box-shaped expanded bead molding.

[0121] Color Tone Unevenness (Appearance): A box-shaped foamed bead molding was placed with the 200mm long x 150mm wide surface facing down and the opening facing up, and 30 measurement positions were randomly set on the lateral side. A spectrophotometer (Konica Minolta Japan, Inc., "CM-5") was used to measure the color tone at these measurement positions, and color coordinates in the CIE 1976 L*a*b* color space were obtained. The color tone was obtained by reflection measurement, with a measurement diameter of φ8 mm and the measurement method being the SCE method. The difference between the maximum and minimum L* values ​​in the color coordinates obtained at the 30 measurement positions described above was evaluated according to the following criteria. ◎: The difference between the maximum and minimum L* values ​​is less than 5. ○: The difference between the maximum and minimum L* values ​​is 5 or more. The L* value is an index of brightness, and the larger the value, the brighter the image. The smaller the difference between the maximum and minimum L* values, the smaller the difference in brightness and the smaller the color unevenness. In addition, the foamed bead moldings in each of the comparative examples were poor in either fusion property or surface property, so that they were not evaluated for uneven color tone.

[0122] [Table 1]

[0123] [Table 2]

[0124] [Table 3]

[0125] [Table 4]

[0126] The above embodiment encompasses the following technical ideas. (1) A method for producing expanded polypropylene-based resin particles, comprising: a dispersing step of dispersing polypropylene-based resin particles in an aqueous medium containing an inorganic dispersant in a container; a foaming agent impregnating step of impregnating the polypropylene-based resin particles with a foaming agent in the container; and a foaming step of releasing the polypropylene-based resin particles containing the foaming agent together with the aqueous medium from the container to foam the particles, the polypropylene-based resin particles have a core layer containing a polypropylene-based resin as a base resin and a coating layer coating the core layer, The coating layer of the polypropylene-based resin particles is composed of a polyethylene-based resin, the coating layer of the polypropylene-based resin particle contains carbon particles and a NOR type hindered amine, The blending ratio of carbon particles in the coating layer of the polypropylene-based resin particles is 0.5% by weight or more and 5% by weight or less, A method for producing expanded polypropylene resin particles, wherein the coating layer of the polypropylene resin particles contains a NOR type hindered amine in an amount of 0.03% by weight or more and less than 1% by weight. (2) The method for producing expanded polypropylene resin particles according to the above (1), wherein the ratio of the NOR type hindered amine content (wt%) to the carbon particle content (wt%) in the coating layer of the polypropylene resin particles is 0.01 or more and 0.2 or less. (3) The method for producing expanded polypropylene resin particles according to (1) or (2) above, wherein the total of the blending ratio (weight %) of the carbon particles and the blending ratio (weight %) of the NOR type hindered amine in the coating layer of the polypropylene resin particles is 1.5 weight % or more and 4 weight % or less. (4) The method for producing expanded polypropylene resin particles according to any one of (1) to (3) above, wherein the carbon particles are carbon black. (5) The method for producing expanded polypropylene resin particles according to any one of (1) to (4) above, wherein the weight ratio of the coating layer in the polypropylene resin particles is 0.5% by weight or more and 10% by weight or less. (6) The bulk density of the polypropylene-based resin foam particles is 10 kg / m 3 More than 60kg / m 3 The method for producing expanded polypropylene resin particles according to any one of the above (1) to (5), which is as follows: (7) The method for producing expanded polypropylene resin particles according to any one of the above (1) to (6), wherein the polyethylene resin is a linear low-density polyethylene polymerized using a metallocene polymerization catalyst. (8) A polypropylene-based resin expanded particle having a foamed core layer made of a polypropylene-based resin as a base resin and a coating layer coating the foamed core layer, The coating layer of the polypropylene-based resin foamed particles is composed of a polyethylene-based resin, the coating layer of the polypropylene-based resin foamed particles contains carbon particles and a NOR type hindered amine, The blending ratio of carbon particles in the coating layer of the polypropylene-based resin expanded particles is 0.5% by weight or more and 5% by weight or less, The expanded polypropylene resin particles have a coating layer containing a NOR type hindered amine in a proportion of 0.03% by weight or more and less than 1% by weight. [Explanation of symbols]

[0127] 10 Polypropylene resin particles 11...Core layer 12, 22...covering layer 20...Polypropylene resin foam particles 21...Foam core layer

Claims

1. A method for producing expanded polypropylene-based resin particles, comprising: a dispersing step of dispersing polypropylene-based resin particles in an aqueous medium containing an inorganic dispersant in a container; a foaming agent impregnating step of impregnating the polypropylene-based resin particles with a foaming agent in the container; and a foaming step of releasing the polypropylene-based resin particles containing the foaming agent together with the aqueous medium from the container to foam the particles, the polypropylene-based resin particles have a core layer containing a polypropylene-based resin as a base resin and a coating layer coating the core layer, The coating layer of the polypropylene-based resin particles is composed of a polyethylene-based resin, the coating layer of the polypropylene-based resin particles contains carbon particles and a NOR-type hindered amine, the blending ratio of carbon particles in the coating layer of the polypropylene-based resin particles is 0.5% by weight or more and 5% by weight or less; The method for producing expanded polypropylene resin particles, wherein the coating layer of the polypropylene resin particles contains a NOR hindered amine in an amount of 0.03% by weight or more and less than 1% by weight.

2. 2. The method for producing expanded polypropylene resin particles according to claim 1, wherein the ratio of the NOR-type hindered amine content (wt%) to the carbon particle content (wt%) in the coating layer of the polypropylene resin particles is 0.01 or more and 0.2 or less.

3. 3. The method for producing expanded polypropylene resin beads according to claim 1, wherein the total of the blending ratio (wt%) of the carbon particles and the blending ratio (wt%) of the NOR-type hindered amine in the coating layer of the polypropylene resin particles is 1.5 wt% or more and 4 wt% or less.

4. The method for producing expanded polypropylene resin beads according to claim 1 , wherein the carbon particles are carbon black.

5. The method for producing expanded polypropylene resin beads according to claim 1 , wherein a weight ratio of the coating layer in the polypropylene resin beads is 0.5% by weight or more and 10% by weight or less.

6. The bulk density of the polypropylene resin foam particles is 10 kg / m 3 More than 60kg / m 3 The method for producing expanded polypropylene resin particles according to any one of claims 1 to 5, wherein the polypropylene resin particles are:

7. The method for producing expanded polypropylene resin particles according to any one of claims 1 to 6, wherein the polyethylene resin is a linear low-density polyethylene polymerized using a metallocene polymerization catalyst.

8. A polypropylene-based resin expanded particle having a foamed core layer made of a polypropylene-based resin as a base resin and a coating layer that coats the foamed core layer, The coating layer of the polypropylene-based resin foamed particles is composed of a polyethylene-based resin, the coating layer of the expanded polypropylene resin particles contains carbon particles and a NOR type hindered amine, the blending ratio of carbon particles in the coating layer of the expanded polypropylene resin particles is 0.5% by weight or more and 5% by weight or less; The expanded polypropylene resin beads are characterized in that the coating layer of the expanded polypropylene resin beads has a blending ratio of NOR type hindered amine of 0.03% by weight or more and less than 1% by weight.

Citation Information

Patent Citations

  • Manufacture of polyolefin-based resin in-mold formed body and polyolefin-based resin in-mold formed body

    JP1992118224A

  • Expanded resin bead

    JP1998077359A

  • Production of foamed polypropylene resin particle, foamed polypropylene resin particle, and molded item thereof

    JP1999147972A

  • In-mold foam molding of polyolefin-based resin

    JP2004263033A

  • Method for producing polypropylene-based resin black foamed particle

    JP2018162370A